SDJ, a pollen-expressed type III J-protein in Prunus, directly binds S-RNase and promotes recruitment of SLFL6 to an S-RNase-associated complex - Xuexi Dou; Daiki Matsumoto; Soichiro Nishiyama; Ryutaro Tao (Plant Reproduction, 2026)

The SbTDR gene is required for anther development and male fertility in Sorghum bicolor - Ashley R. Smith; Jian Huang; Uyiosasere D. Aigbe; Xia Wan; Junping Chen; Zhanguo Xin; Dazhong Zhao (Plant Reproduction, 2026)
Anthers are essential in plant reproduction and are also crucial in agriculture, because hybrid seed production typically relies on the manipulation of male fertility. Sorghum ( Sorghum bicolor L. Moench) is the fifth most produced grain crop in the world. However, relatively little is known about the genetic mechanisms that regulate anther development and male fertility in sorghum. Here, we report the morphological characterization of anther development in wild-type sorghum BTx623 and the Sorghum bicolor tapetal degeneration retardation ( Sbtdr ) mutant, as well as identification of the causal gene SbTDR . Our results showed that the Sbtdr mutant formed small, white anthers that failed to produce pollen grains. We classified sorghum anther development into 13 main stages based on major cellular landmarks observed in semi-thin sections of anthers. Our analysis demonstrated that the Sbtdr mutant is defective in tapetal cell degeneration. Moreover, in situ hybridization revealed that the SbTDR gene, which encodes a bHLH transcription factor, is primarily expressed in tapetal cells at the microspore stage. Our discoveries highlight the importance of the SbTDR bHLH transcription factor in controlling tapetal cell differentiation and male sterility, which may help develop novel hybrid breeding systems in sorghum.

Close contact: role of the extracellular matrix in cell adhesion and separation during plant development and reproduction - Juliette Cremer; Marc Ropitaux; Arnaud Lehner; Jean-Claude Mollet (Plant Reproduction, 2026)

PbrFEN-1 positively regulates pear pollen tube growth and is involved in the self-incompatibility response - Zhi-Heng Sui; Yi-Peng Ye; Ju-Yang Yao; Ya-Ru Wang; Ying Xu; Ce-Xian Cui; Shao-Ling Zhang; Chao Gu (Plant Reproduction, 2026)

Apomixis frequency in polyploid wild populations of Psidium cattleyanum f. lucidum (Myrteae, Myrtaceae) - Mercedes Souza-Pérez; Raquel Machado; Magdalena Vaio; Alejandra Borges; José I. Hormaza; Gabriela Speroni (Plant Reproduction, 2026)

Morphological basis for the development of pistillate and staminate florets in a dioecious species of Poa (Poeae, Pooideae, Poaceae) - Juca A. B. San Martin; Abelardo C. Vegetti; Raúl E. Pozner; Nora G. Uberti Manassero; Carlos A. Dezar; Liliana M. Giussani; Andrea G. Reutemann (Plant Reproduction, 2026)

Basis of apomixis in flowering plants – state of the art and research perspectives - Agnieszka Barbara Springer; Krystyna Musiał (Plant Reproduction, 2026)
In most angiosperm plants, seeds are produced through a sexual process. Some angiosperms have developed an alternative reproductive strategy termed apomixis which involves producing seeds without the key steps of sexual development (i.e. meiosis, fertilization) and results in progeny genetically identical to the mother plant. Despite significant research advances, the evolutionary origin and molecular nature of apomixis remain unclear. Recent findings suggest that apomixis may have emerged from a sexual pathway deregulated by genetic and epigenetic modifications and stress signals (both endogenous and exogenous) that led to the alteration or omission of selected stages of sexual development. Apomixis, as a natural phenomenon that enables clonal reproduction by seeds, is a desirable trait with great potential in plant breeding, especially in terms of preserving hybrid vigor and gene combinations of elite phenotypes over subsequent generations. Notwithstanding, apomixis does not occur in major crops and therefore research programs focus on how to introgress, induce, or mimic apomixis in agronomically significant sexual species. The present review outlines the history of research on apomixis in flowering plants, its mechanisms, and a summary of the latest and most impactful research advances that may pave the way for the introduction of apomixis to sexually reproducing crops. The reader’s attention is also drawn to the partially explained issue of intercellular communication in ovules during early apomictic processes in the context of the cell wall’s changed chemical composition in cells that enter the apomictic developmental pathway.

SWI3A/B regulates the transition from vegetative to reproductive phase in the liverwort Marchantia polymorpha - Maria Lozano-Quiles; Parth K. Raval; Stefan A Rensing; Sven B. Gould (Plant Reproduction, 2026)
Land plants alternate between multicellular haploid and diploid phases, requiring a tight coordination between vegetative growth and sexual reproduction. We investigated SWI3A/B , an ancient core subunit of the SWI/SNF complex, of the non-vascular liverwort Marchantia polymorpha . A mutation in the promoter of Mp SWI3A/B affected gametangiophore development and spermiogenesis in males, revealing its male-specific role in reproductive development. The Mp SWIA/B mutant line amplifies vegetative propagation in males under conditions that would normally induce reproductive growth. The phenotype was underpinned by transcriptomic changes, showing that MpSWI3A/B modulates key regulators of gametangiophore initiation (e.g. BONOBO, GLID), sperm development and motility (e.g. DUO1, PKAR), and asexual reproduction (e.g. KAI2). We propose that, as a chromatin-level regulator, MpSWI3A/B may contribute to balancing vegetative and reproductive phases and highlight the protein’s potential when exploring ancient epigenetic functions that coordinate developmental phase transitions in land plants.

Characterization of TERMINAL FLOWER 1 homologs from Macroptilium (Benth.) Urb - Yemina Rocío Abelendo; Nicolás Arizpe David; Andrea Gabriela Sarmiento; Juan Marcelo Zabala; Karina Fabiana Ribichich (Plant Reproduction, 2026)

Low-temperature stress modulates pollen tube growth through temperature-dependent multi-level regulatory mechanisms in Camellia sinensis - Sena Acar; Aslıhan Çetinbaş-Genç (Plant Reproduction, 2026)
Low temperature is a major environmental stress factor that limits male reproductive success in plants; however, the mechanistic basis of pollen responses to different degrees of low temperature stress remains poorly understood. In this study, we investigated the cytological, biochemical, and molecular responses of tea ( Camellia sinensis ) pollen grains to low-temperature stress by germinating pollen in vitro at 15, 10, and 5 °C. Although pollen germination rate and pollen tube length were reduced under all low-temperature treatments compared with the control, the underlying regulatory responses differed significantly with the severity of low-temperature stress. At 15 °C, decreases in non-enzymatic antioxidants and stress-related proteins indicated an overall metabolic weakening, while the concomitant accumulation of callose, cellulose, and methyl-esterified pectins reflected an early structural adjustment of the pollen tube cell wall. At 10 °C, the increasing stress load was partially counterbalanced by the induction of enzymatic antioxidant activities, and continued cell wall reinforcement identified this temperature as a transitional state between metabolic limitation and coordinated defense activation. In contrast, exposure to 5 °C resulted in pronounced metabolic suppression, together with a shift of stress-related proteins toward membrane fractions and enhanced deposition of callose, cellulose, and particularly de-esterified acidic pectins, leading to increased cell wall rigidity and mechanical restriction of pollen tube elongation. Overall, this study demonstrates that low-temperature stress constrains pollen tube growth not through a single limiting factor but via a temperature-dependent reorganization of interconnected cytological, biochemical, and molecular mechanisms.

Beyond the pollen dilemma: a case of heteranthery driven by pollinator attraction in Mamedea pulchella (Malpighiaceae), an oil-rewarding species - Marina Gotelli; Florencia Verón Schöenfeld; Juan Ignacio Agüero; Juan Pablo Torretta; Sandra Aliscioni (Plant Reproduction, 2026)

Single and multiple buds form characteristics in Amorphophallus muelleri - YaXin Liu; ZeMei Li; JinDi He; WenHan Li; YuQi Xie; SiYi Ge; RuiJia Wang; XueWei Wu (Plant Reproduction, 2026)

A staging framework to study rice female gametophyte development - Taehoon Kim; Divya Rana; Isabel Ocampo-Quiceno; Kevin Begcy (Plant Reproduction, 2026)

Bridging the gaps: advanced techniques to unlock lipid function in plant reproductive development - Ze-Hua Guo; Mee-Len Chye (Plant Reproduction, 2025)
In plant cells, lipids serve various roles facilitating membrane bilayer formation, energy storage and signaling molecules. Acyl lipids are the most common in distinct plant cell compartments. Lipids regulated by key genes encoding fatty acid desaturases, diacylglycerol acyltransferase, 3-ketoacyl-CoA synthase and acyl-CoA-binding proteins (ACBPs) are deemed crucial during floral development. ACBPs, along with long-chain acyl-CoA synthase, acetyl-CoA carboxylase, fatty acid synthase, acyl-acyl carrier protein desaturases, acyl-ACP thioesterases and the ATP-binding cassette transporter subfamily A, contribute to fatty acid (FA) production, lipid transport and seed oil accumulation, making them bioengineering targets. To investigate lipid function, it is important to use appropriate analytical strategies because different lipid classes contain distinct FA patterns. These well-developed techniques include advanced lipidomic studies using multi-dimensional liquid chromatography-mass spectrometry, matrix-assisted laser desorption/ionization mass spectrometry imaging, lipid-binding assays and x-ray crystallography. As these techniques continue to evolve, further updates on lipid function are expected to rapidly materialize.

Mechanosensitive ion channel MSL8 is required for oscillatory growth and cell wall dynamics in Arabidopsis pollen tubes - Joshua H. Coomey; Elizabeth S. Haswell (Plant Reproduction, 2025)

Hormones and plant reproduction - Nayelli Marsch-Martinez; Lars Østergaard; Paula McSteen; Dolf Weijers (Plant Reproduction, 2025)

Abnormal hypophyseal and suspensor divisions in Arabidopsis dcl1 embryos are not attributable to a single miR156-targeted SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) gene, but likely involve redundant genetic pathways and/or modulation by genetic background - Andrea Tovar-Aguilar; Jianfei Zhao; Scott Poethig; Stewart Gillmor (Plant Reproduction, 2025)
Key message Loss of SPL10 and SPL11 increases penetrance of abnormal phenotypes in dcl1 embryos. Abstract The first division of the Arabidopsis zygote is asymmetric, resulting in an apical cell lineage that generates most of the embryo proper, and a basal cell lineage that produces the root meristem and the extraembryonic suspensor. Loss of function mutations in the microRNA processing enzyme genes DICER-LIKE 1 (DCL1) and SERRATE (SE) show cell division defects in the embryo proper, hypophyseal cell, and suspensor. Previous transcriptome analyses showed that the microRNA156-targeted transcription factor genes SQUAMOSA PROMOTER BINDING PROTEIN-LIKE2 (SPL2) , SPL3 and SPL11 were upregulated in both globular stage dcl1 and se embryos, while SPL10 was upregulated in dcl1 . It was previously proposed that upregulation of SPL10 and SPL11 could explain some abnormal phenotypes in dcl1 embryos. In this work, we used T-DNA and CRISPR-Cas9-induced loss of function alleles to further explore the function of SPL2 , SPL3 , SPL10 and SPL11 in early embryogenesis and their contribution to the dcl1 phenotype. On their own, spl2 , spl3 , spl10 , and spl11 single mutants and an spl10 spl11 double mutant showed no abnormal cell divisions in early embryogenesis. In the dcl1/+ background, loss of function of SPL2 or SPL3 did not change the proportion of cell division defects in hypophyseal cells or suspensors observed in dcl1/+ . Loss of spl10 or spl11 in dcl1/+ resulted in a slight decrease or increase (respectively) in the penetrance of abnormal suspensor divisions in heart stage embryos, while the spl10 spl11 double mutant caused a small increase in the penetrance of abnormal hypophyseal divisions in dcl1 embryos. The differences between our results and previous studies are likely due to genetic redundancy of miR156-targeted SPL genes, variable environmental conditions or the effect of genetic background on the penetrance of the dcl1 phenotype. In the future, analysis of higher order mutations in SPL and MIR156 genes will help to better understand the role of these important developmental regulators in early embryo development.

Meiotic cytokinesis defects in cultured Arabidopsis flowers induce diploid microspores - Huiqi Fu; Yuting Chen; Xueying Cui; Huishan He; Jingru Wang; Chong Wang; Ziming Ren; Bing Liu (Plant Reproduction, 2025)

Spatial organization and trafficking dynamics of ANX/BUPS-RALF-LLG signaling complexes during pollen tube growth - Patricia L. Seitz; Li-Jia Qu; Thomas Dresselhaus; Liang-Zi Zhou (Plant Reproduction, 2025)

BONOBO transcription factors positively regulate STICKY GENERATIVE CELL for generative cell internalisation in Arabidopsis - Sung-Aeong Oh; Soon Ki Park (Plant Reproduction, 2025)

Semi-automated high content analysis of pollen performance using tubetracker - Sorel V. Yimga Ouonkap; Yahir Oseguera; Bryce Okihiro; Mark A. Johnson (Plant Reproduction, 2025)

The regulation of vacuole morphology in stigma papilla cells is involved in water transfer to pollen in Arabidopsis thaliana - Kazuki Fukushima; Maki Hayashi; Masao Watanabe (Plant Reproduction, 2025)
Key message The stigma papilla cells of Arabidopsis thaliana control water transport to pollen by regulating the morphology of vacuoles in papilla cells after pollination. Abstract Pollen hydration is the first crucial response after pollination for successful fertilization. In the Brassicaceae family, papilla cells on the stigma supply water to pollen. In pollinated papilla cells, cellular responses essential for pollen hydration are induced. However, it remains unclear how papilla cells release water from inside the cells to the pollen. Here, we set up a live-cell imaging system for observing vacuole dynamics in Arabidopsis thaliana papilla cells and investigated the role of vacuole morphology in these cells in the regulation of water transfer to pollen. Before pollination, vacuoles in the papilla cells changed their morphology through fusion and constriction; however, after pollination, they formed larger vacuoles and exhibited reduced movement. Additionally, when the morphological variation of vacuoles in the papilla cells was inhibited by wortmannin treatment, the pollen hydration rate decreased in a concentration-dependent manner. In contrast, the vacuoles tended to be less constricted even before pollination and showed less variation than wild-type after pollination in Rho-like GTPase from plants 2 (ROP2) mutant papilla cells, where the pollen hydration rate is faster. We propose that the regulation of vacuole morphology in papilla cells is involved in water transfer to pollen during pollination.

ROS regulation of stigma papillae growth and maturation in Arabidopsis thaliana - Subramanian Sankaranarayanan; Sowmiya D. Venkatesan; Thomas C. Davis; Sharon A. Kessler (Plant Reproduction, 2025)
Key message Superoxide accumulates during early stigma papillae growth stages in Arabidopsis. Abstract Highly specialized stigma papillae cells play a critical role in plant reproduction. Their main purpose is to catch and interact with pollen, to mediate compatibility responses, to regulate pollen germination, and to guide pollen tubes to the transmitting tract so that the sperm cells carried in the pollen can be delivered to the female gametophyte to achieve double fertilization. In Arabidopsis thaliana , the stigma consists of single-celled stigma papillae that emerge from the apex of the fused carpels. Despite their critical function in plant reproduction, the molecular mechanisms that govern growth and maturation of stigma papillae remain poorly understood. Reactive Oxygen Species (ROS) have been implicated in stigma receptivity, but their roles in papillae development are less explored. Here we show that reactive oxygen species (ROS) also play different roles in stigma papillae development, with superoxide accumulating during the initiation and growth phase and hydrogen peroxide accumulating in mature papillae that are receptive to pollen. Reducing superoxide levels in the stigma by pharmacological treatments or over-expressing superoxide dismutase enzymes under an early stigma promoter inhibited stigma papillae growth, suggesting that ROS homeostasis is critical to papillae growth and differentiation for optimal pollination.

Anisotropic diffuse growth in Arabidopsis thaliana stigma papillae - Thomas C. Davis; Sharon A. Kessler (Plant Reproduction, 2025)
Key message Arabidopsis stigma papillae grow by a diffuse growth mechanism rather than by tip growth. Abstract In angiosperms, the stigma is the first point of contact between the pollen (male) and pistil (female) during pollination. The stigma facilitates pollen capture and adhesion, compatibility responses, pollen germination, and pollen tube guidance to the transmitting tract. In Arabidopsis thaliana , the stigma is composed of single-celled stigma papillae that initiate from the apex of the carpels. Despite their critical function in plant reproduction, little is known about the cell and molecular mechanisms that govern stigma papillae growth and development. Using morphometric analysis of stigma papillae growth during different stages of floral development, we show that A. thaliana stigma papillae grow via a diffuse growth mechanism. Consistent with this conclusion, several mutants with reduced growth anisotropy in vegetative tissues due to defective cellulose or microtubule function likewise reduce anisotropy in stigma papillae.

Sexual reproduction in land plants: an evolutionary perspective - Annette Becker; Xia Chen; Thomas Dresselhaus; Nora Gutsche; Stefanie J. Müller-Schüssele; Stefanie Sprunck; Günter Theißen; Sophie de Vries; Sabine Zachgo (Plant Reproduction, 2025)
Key message We link key aspects of land plant reproductive evolution and detail how successive molecular changes leading to novel tissues and organs require co-evolution of communication systems between tissues. Abstract The transition of water-dependent reproduction of algae to mechanisms with very limited water dependence in many land plant lineages allowed plants to colonize diverse terrestrial environments, leading to the vast variety of extant plant species. The emergence of modified cell types, novel tissues, and organs enabled this transition; their origin is associated with the co-evolution of novel or adapted molecular communication systems and gene regulatory networks. In the light of an increasing number of genome sequences in combination with the establishment of novel genetic model organisms from diverse green plant lineages, our knowledge and understanding about the origin and evolution of individual traits that arose in a concerted way increases steadily. For example, novel members of gene families in signaling pathways emerged for communication between gametes and gametophytes with additional tissues surrounding the gametes. Here, we provide a comprehensive overview on the origin and evolution of reproductive novelties such as pollen grains, immobile sperms, ovules and seeds, carpels, gamete/gametophytic communication systems, double fertilization, and the molecular mechanisms that have arisen anew or have been co-opted during evolution, including but not limited to the incorporation of phytohormones, reactive oxygen species and redox signaling as well as small RNAs in regulatory modules that contributed to the evolution of land plant sexual reproduction.

Haustorial processes during the female gametophyte formation in Rosularia pallida (Schott & Kotschy) Stapf (Crassulaceae) - Emilia Brzezicka; Małgorzata Kozieradzka-Kiszkurno (Plant Reproduction, 2025)

Potential regulation of cleistogamy in pigeonpea through jasmonic acid and bHLH transcription factor interactions - Palak Gupta; Harsha Srivastava; Kuldeep Kumar; Machindra Nirgude; Kumari Arpita; Jyothilakshmi Vadassery; Sandhya Sharma; Malik Zainul Abdin; Kishor Gaikwad (Plant Reproduction, 2025)

Providence 2024: meeting of the International Association of Sexual Plant Reproduction Research - Naoya Sugi; Sarita Muñoz-Gómez; Daniel S. Jones (Plant Reproduction, 2025)

A review on the function of arabinogalactan-proteins during pollen grain development - Sara Foubert-Mendes; Jessy Silva; Maria João Ferreira; Luís Gustavo Pereira; Sílvia Coimbra (Plant Reproduction, 2025)
Key message Overview of the current understanding of PG development, PT growth and the role of AGPs in these processes. Abstract The pollen grain (PG) is a complex structure composed of three cells: the vegetative cell which develops into a pollen tube (PT) and two sperm cells that will fuse with the egg cell and central cell, giving rise to the embryo and endosperm, respectively. This resilient gametophyte is constantly subjected to selective pressures, leading to a diverse range of characteristics, with one of its defining features being the pollen cell wall. In this review, we closely examine the developmental stages of PG formation and PT growth, with a specific focus on the dynamic roles of arabinogalactan-proteins (AGPs) throughout these processes. AGPs are initially present in pollen mother cells and persist throughout PT growth. In the early stages, AGPs play a crucial role in primexine anchoring, followed by nexine and intine formation as well as cellulose deposition, thereby providing essential structural support to the PG. As PGs mature, AGPs continue to be essential, as their absence often leads to the collapse of PGs before they reach full maturity. Moreover, the absence of AGPs during PT growth leads to abnormal growth patterns, likely due to disruptions of cellulose, callose, and F-actin deposition, as well as perturbations in calcium ion (Ca 2+ ) signalling. Understanding the intricate interplay between AGPs and PG development sheds light on the underlying mechanisms that drive reproductive success and highlights the indispensable role of AGPs in ensuring the integrity and functionality of PGs.

Decay of self-incompatibility within a lifespan in Physalis acutifolia (Solanaceae) - Chelsea Pretz; Erica Au; Stacey D. Smith (Plant Reproduction, 2025)
Key message Self-incompatibility decays with age in plants of Physalis acutifolia , and plants that have transitioned to selfing produce fewer seeds but with comparable viability. Self-compatibility in this system is closely related to flower size, which is in turn dependent on the direction of the cross, suggesting parental effects on both morphology and compatibility. Abstract The sharpleaf groundcherry, Physalis acutifolia , is polymorphic for self-compatibility, with naturally occurring self-incompatible (SI) and self-compatible (SC) populations. Moreover, SI individuals have been documented to transition to SC with age, at least in greenhouse conditions. Here we tested whether this within-lifespan transition occurs predictably (developmental decay of SI) or could result from a lack of pollination (a plastic response). Using greenhouse crosses, we demonstrated that SI P. acutifolia plants transition to SC after 70 days, regardless of pollination treatment, consistent with predictable developmental decay. This loss of SI corresponds to a loss of pollen inhibition, with self-pollen often reaching the ovary after 24 h. The originally SI plants that transition to SC can produce viable seeds from self crosses, albeit significantly fewer than from outcrosses of SI plants or from lines fixed for SC. Throughout the experiment, we observed that flower size, which differs between SI and SC populations, was highly correlated with the compatibility phenotype. These findings suggest that the mechanisms leading to the loss of SI during a lifespan are similar to those involved in fixed losses of SI, but that older plants that transition to SC do not present the same reproductive capacity as fixed selfers.

The MADS-box protein SHATTERPROOF 2 regulates TAA1 expression in the gynoecium valve margins - Subodh Verma; Lenka Švihlová; Hélène S. Robert (Plant Reproduction, 2025)
Key message SHATTERPROOF 2 regulates TAA1 expression for the establishment of the gynoecium valve margins. Abstract Gynoecium development and patterning play a crucial role in determining the ultimate structure of the fruit and, thus, seed production. The MADS-box transcription factor SHATTERPROOF 2 (SHP2) contributes to valve margin differentiation and plays a major role in fruit dehiscence and seed dispersal. Despite the acknowledged contribution of auxin to gynoecium development, its precise role in valve margin establishment remains somewhat enigmatic. Our study addresses this gap by uncovering the role of SHP2 as a positive regulator of key auxin biosynthetic genes, TAA1 and YUCCA 4 . Genetic and molecular analyses revealed that SHP2 directly regulates the expression of TAA1 in the valve margins of a stage 12 gynoecium with known regulators of flower and ovule development, such as AGAMOUS, SEEDSTICK, and SEPATALA 3. Collectively, our findings define a previously unrecognized function of SHP2 in the regulation of auxin biosynthetic genes during gynoecium development and raise the possibility that the auxin produced under SHP2 regulation may contribute significantly to the valve margin establishment.

Hormonal regulation and crosstalk during early endosperm and seed coat development - R. Pankaj; R. B. Lima; D. D. Figueiredo (Plant Reproduction, 2025)
Key message This review covers the latest developments on the regulation of early seed development by phytohormones. Abstract The development of seeds in flowering plants starts with the fertilization of the maternal gametes by two paternal sperm cells. This leads to the formation of two products, embryo and endosperm, which are surrounded by a tissue of maternal sporophytic origin, called the seed coat. The development of each of these structures is under tight genetic control. Moreover, several phytohormones have been shown to modulate the development of all three seed compartments and have been implicated in the communication between them. This is particularly relevant, as embryo, endosperm, and seed coat have to coordinate their development for successful seed formation. Here, we review the latest advances on the hormonal regulation of early seed development in the model plant species Arabidopsis thaliana , with a focus on the endosperm and the seed coat. Moreover, we highlight how phytohormones serve as mechanisms of non-cell autonomous communication between these two compartments and how they are determinant in shaping seed formation.

Integrating single nuclei and bulk RNA sequencing in rice shoot apical meristems uncovers candidate early floral transition gene networks - Daniele Traversa; Giulio Vicentini; Paolo Korwin Krukowski; Lucio Conti; Matteo Chiara; Vittoria Brambilla (Plant Reproduction, 2025)

Twin embryo formation by induced parthenogenesis - Hannah Peha; Hui Ren; Debra Skinner; Venkatesan Sundaresan (Plant Reproduction, 2025)

From lock and key to molecular diplomacy: understanding pollen recognition and discrimination in brassicaceae - Hemal Bhalla; Kumari Ankita; Kumar Abhinandan; Trivima Sharma; Subramanian Sankaranarayanan (Plant Reproduction, 2025)

Cellular mechanism of polarized auxin transport on fruit shape determination revealed by time-lapse live imaging - Yao Zhang; Hao-Ran Sun; Zhi-Cheng Hu; Yang Dong (Plant Reproduction, 2025)

Hormonal influence on maize inflorescence development and reproduction - Amina Chaudhry; Zongliang Chen; Andrea Gallavotti (Plant Reproduction, 2024)
Key message Different plant hormones contribute to maize reproductive success. Abstract Maize is a major crop species and significantly contributes directly and indirectly to human calorie uptake. Its success can be mainly attributed to its unisexual inflorescences, the tassel and the ear, whose formation is regulated by complex genetic and hormonal networks, and is influenced by environmental cues such as temperature, and nutrient and water availability. Traditional genetic analysis of classic developmental mutants, together with new molecular approaches, have shed light on many crucial aspects of maize reproductive development including the influence that phytohormones exert on key developmental steps leading to successful reproduction and seed yield. Here we will review both historical and recent findings concerning the main roles that phytohormones play in maize reproductive development, from the commitment to reproductive development to sexual reproduction.

The plant early recombinosome: a high security complex to break DNA during meiosis - Nahid Rafiei; Arnaud Ronceret (Plant Reproduction, 2024)
Key message The formacion of numerous unpredictable DNA Double Strand Breaks (DSBs) on chromosomes iniciates meiotic recombination. In this perspective, we propose a ‘multi-key lock’ model to secure the risky but necesary breaks as well as a ‘one per pair of cromatids’ model for the topoisomerase-like early recombinosome. Abstract During meiosis, homologous chromosomes recombine at few sites of crossing-overs (COs) to ensure correct segregation. The initiation of meiotic recombination involves the formation of DNA double strand breaks (DSBs) during prophase I. Too many DSBs are dangerous for genome integrity: if these DSBs are not properly repaired, it could potentially lead to chromosomal fragmentation. Too few DSBs are also problematic: if the obligate CO cannot form between bivalents, catastrophic unequal segregation of univalents lead to the formation of sterile aneuploid spores. Research on the regulation of the formation of these necessary but risky DSBs has recently advanced in yeast, mammals and plants. DNA DSBs are created by the enzymatic activity of the early recombinosome, a topoisomerase-like complex containing SPO11. This opinion paper reviews recent insights on the regulation of the SPO11 cofactors necessary for the introduction of temporally and spatially controlled DSBs. We propose that a ‘multi-key-lock’ model for each subunit of the early recombinosome complex is required to secure the formation of DSBs. We also discuss the hypothetical implications that the established topoisomerase-like nature of the SPO11 core-complex can have in creating DSB in only one of the two replicated chromatids of early prophase I meiotic chromosomes. This hypothetical ‘one per pair of chromatids’ DSB formation model could optimize the faithful repair of the self-inflicted DSBs. Each DSB could use three potential intact homologous DNA sequences as repair template: one from the sister chromatid and the two others from the homologous chromosomes.

The Arabidopsis KASH protein SINE3 is involved in male and female gametogenesis - Morgan Moser; Norman R. Groves; Iris Meier (Plant Reproduction, 2024)
Key message The Arabidopsis KASH protein SINE3 is involved in male and female gametophyte development, likely affecting the first post-meiotic mitosis in both cases, and is required for full seed set. Abstract Linker of nucleoskeleton and cytoskeleton (LINC) complexes are protein complexes spanning the inner and outer membranes of the nuclear envelope (NE) and are key players in nuclear movement and positioning. Through their roles in nuclear movement and cytoskeletal reorganization, plant LINC complexes affect processes as diverse as pollen tube rupture and stomatal development and function. KASH proteins are the outer nuclear membrane component of the LINC complex, with conserved C-termini but divergent N-terminal cytoplasmic domains. Of the known Arabidopsis KASH proteins, SUN-INTERACTING NUCLEAR ENVELOPE PROTEIN 3 (SINE3) has not been functionally characterized. Here, we show that SINE3 is expressed at all stages of male and female gametophyte development. It is located at the NE in male and female gametophytes. Loss of SINE3 results in a female-derived seed set defect, with sine3 mutant ovules arresting at stage FG1. Pollen viability is also significantly reduced, with microspores arresting prior to pollen mitosis I. In addition , sine3 mutants have a minor male meiosis defect, with some tetrads containing more than four spores. Together, these results demonstrate that the KASH protein SINE3 plays a crucial role in male and female gametophyte development, likely affecting the first post-meiotic nuclear division in both cases.

Localization and activity of lipoxygenase in the ovule of Larix kaempferi (Lamb.) Carr. during female gametophyte maturation - Aleksandra Seta-Koselska; Ewa Szczuka; Mateusz Koselski (Plant Reproduction, 2024)
Key message Lipoxygenase activity and localization vary throughout the development of Larix kaempferi ovules, with the highest enzyme activity observed in ovules at the cellular stage and the most intense immunogold reaction noted at the mature archegonium stage of gametophyte development. Abstract Lipoxygenases are a family of oxidoreductases with a significant role in biological systems, widespread in living organisms e.g. mammals, fish, corals, plants, mosses, algae, fungi, yeasts, and bacteria. Lipoxygenase activity in plants leads to the formation of phytooxylipins, i.e. signaling molecules, which play a crucial role in many significant physiological processes such as male and female gametophyte maturation, germination and seedling growth, pathogen resistance, abiotic stress response, fruit ripening, and senescence. The activity and localization of lipoxygenase change during plant growth and development. The localization of lipoxygenase in a developing ovule of Larix kaempferi was analyzed using the immunogold labeling method, and the activity was determined spectrophotometrically with linolenic acid as a substrate. Among the investigated stages, the immunogold reaction was the most intense at the mature archegonium stage in the ovule. Lipoxygenase was found in all parts of the L. kaempferi ovule. The largest number of immunogold particles was detected in the integument cells of all the analyzed stages of ovule development. Only one isoform of lipoxygenase with an optimum at pH 8 was active in the ovules during female gametophyte maturation. The highest enzyme activity was determined at the cellular stage, whereas the mature archegonium stage was characterized by its lowest level, which means that LOX activity in developing ovules of the Japanese larch is not correlated with the number of antibody-labeled molecules of the enzyme.

Application of genome editing in plant reproductive biology: recent advances and challenges - Nilesh D. Gawande; Hemal Bhalla; Anshul Watts; Rahul Mahadev Shelake; Subramanian Sankaranarayanan (Plant Reproduction, 2024)

AtHMGB15 regulates tapetal apoptosis in pollen development and actin dynamics during pollen germination in arabidopsis - Ruby Biswas; Shubho Chaudhuri (Plant Reproduction, 2024)

Identification of male sterility-related genes in Saccharum officinarum and Saccharum spontaneum - Jinjin Song; Xiaodan Zhang; Tyler Jones; Ming-Li Wang; Ray Ming (Plant Reproduction, 2024)

An epiQTL underlying asexual seed formation in Arabidopsis - Rishabh Pankaj; Shiana Shoejaeyfar; Duarte D. Figueiredo (Plant Reproduction, 2024)
Key message The DNA methylation status at an epigenetic quantitative trait locus in the Arabidopsis chromosome 2 is linked to the formation of apomictic-like endosperms. Abstract Seed development in most angiosperms is coupled to fertilization of the maternal gametes by two sperm cells. However, apomictic species can reproduce asexually via seeds. This trait is of great agricultural interest, as it would fix complex genotypes and allow for pollen-independent seed production. However, engineering full apomixis requires three independent processes: apomeiosis, parthenogenesis and autonomous endosperm development. While the first two have been successfully engineered in some crops, the formation of autonomous endosperms remains a challenge. Although it is known that this trait is under epigenetic control, such as of DNA methylation, the underlying mechanisms remain mostly undiscovered. Here, using epigenetic recombinant inbred lines, we identified an epigenetic quantitative trait locus in the Arabidopsis chromosome 2, which correlates with permissiveness for the formation of asexual seeds: hypomethylation at this genomic region allows the formation of larger autonomous endosperms. Importantly, the methylation at this locus only correlates with asexual seed size, and not to the size of sexual seeds or that of other organs. With this, we aim to show that screening for epialleles is a promising strategy to uncover loci underlying relevant traits and could pave the way to identifying genes necessary for the engineering of apomixis.

Pectin methylesterase activities in reproductive tissues of maize plants with different haplotypes of the Ga1 and Ga2 cross incompatibility systems - Amruta R. Bapat; M. Paul Scott (Plant Reproduction, 2024)
Key message Total PME activity in reproductive tissues was related to haplotypes at maize cross incompatibility loci, suggesting that these loci function by controlling PME activity. Abstract In maize, the pollination outcome depends on the haplotypes of the interacting male gametophyte (germinated pollen) and female sporophyte (silk) at several cross-incompatibility loci. Functional alleles (- S haplotypes) of the cross-incompatibility loci Ga1 and Ga2, both encode two pectin methylesterases (PMEs), one that is expressed in silk and the other in pollen. We examined total PME activity in reproductive tissues containing functional and null haplotypes at the Ga1 or Ga2 loci. In pollinated silks, there was a correlation between total PME activity and the -S haplotype pollen in both Ga1 and Ga2 systems. We did not detect a significant relationship between PME activity and pollination outcome of either system. We re-examined previously reported active site amino acid substitutions in PMEs encoded by cross incompatibility loci. We observed that different active site substitutions are present in the pollen and silk PMEs of cross incompatibility loci and these differences are conserved across Ga1 , Ga2 and Tcb-1 . This work establishes a relationship between total PME activity and the haplotypes of the Ga1 locus in pollinated silks.

Revisit and explore the ethylene-independent mechanism of sex expression in cucumber (Cucumis sativus) - Nguyen Hoai Nguyen; Phuong Thi Bich Ho; Linh Thi Truc Le (Plant Reproduction, 2024)

A novel strategy to study apomixis, automixis, and autogamy in plants - Petra Šarhanová; Ľuboš Majeský; Michal Sochor (Plant Reproduction, 2024)
Key message The combination of a flow cytometric seed screen and genotyping of each single seed offers a cost-effective approach to detecting complex reproductive pathways in flowering plants. Abstract Reproduction may be seen as one of the driving forces of evolution. Flow cytometric seed screen and genotyping of parents and progeny are commonly employed techniques to discern various modes of reproduction in flowering plants. Nevertheless, both methods possess limitations constraining their individual capacity to investigate reproductive modes thoroughly. We implemented both methods in a novel manner to analyse reproduction pathways using a carefully selected material of parental individuals and their seed progeny. The significant advantage of this approach lies in its ability to apply both methods to a single seed. The introduced methodology provides valuable insights into discerning the levels of apomixis, sexuality, and selfing in complex Rubus taxa. The results may be explained by the occurrence of automixis in Rubus , which warrants further investigation. The approach showcased its effectiveness in a different apomictic system, specifically in Taraxacum . Our study presents a comprehensive methodological approach for determining the mode of reproduction where flow cytometry loses its potential. It provides a reliable and cost-effective method with significant potential in biosystematics, population genetics, and crop breeding.

“Resilience in crop reproduction for food security: introducing RECROP COST action” - Sotirios Fragkostefanakis; Michal Lieberman-Lazarovich; David Honys (Plant Reproduction, 2024)

Ectopic expression of a thaumatin-like protein impairs the timely deposition and dissolution of callose during microsporogenesis, leading to microspore death and male sterility in Arabidopsis - Sung-Aeong Oh; Soon Ki Park (Plant Reproduction, 2024)

Distinctive development of embryo and endosperm caused by male gametes irradiated with carbon-ion beam - Tomonari Hirano; Muneaki Murata; Yurie Watarikawa; Yoichiro Hoshino; Tomoko Abe; Hisato Kunitake (Plant Reproduction, 2024)
Key message In Cyrtanthus mackenii , development of embryo and endosperm were differentially affected by fertilization of male gametes with DNA damage and mutations. Abstract Pollen irradiation with ionizing radiations has been applied in plant breeding and genetic research, and haploid plant induction has mainly been performed by male inactivation with high-dose irradiation. However, the fertilization process of irradiated male gametes and the early development of embryo and endosperm have not received much attention. Heavy-ion beams, a type of radiation, have been widely applied as effective mutagens for plants and show a high mutation rate even at low-dose irradiation. In this study, we analyzed the effects of male gametes of Cyrtanthus mackenii irradiated with a carbon-ion beam at low doses on fertilization. In immature seeds derived from the pollination of irradiated pollen grains, two types of embryo sacs were observed: embryo sac with a normally developed embryo and endosperm and embryo sac with an egg cell or an undivided zygote and an endosperm. Abnormalities in chromosome segregation, such as chromosomal bridges, were observed only in the endosperm nuclei, irrespective of the presence or absence of embryogenesis. Therefore, in Cyrtanthus , embryogenesis is strongly affected by DNA damage or mutations in male gametes. Moreover, various DNA contents were detected in the embryo and endosperm nuclei, and endoreduplication may have occurred in the endosperm nuclei. As carbon-ion irradiation causes chromosomal rearrangements even at low doses, pollen irradiation can be an interesting tool for studying double fertilization and mutation heritability.

JAGGER localization and function are dependent on GPI anchor addition - Raquel Figueiredo; Mónica Costa; Diana Moreira; Miguel Moreira; Jennifer Noble; Luís Gustavo Pereira; Paula Melo; Ravishankar Palanivelu; Sílvia Coimbra; Ana Marta Pereira (Plant Reproduction, 2024)
Key message GPI anchor addition is important for JAGGER localization and in vivo function. Loss of correct GPI anchor addition in JAGGER, negatively affects its localization and function. Abstract In flowering plants, successful double fertilization requires the correct delivery of two sperm cells to the female gametophyte inside the ovule. The delivery of a single pair of sperm cells is achieved by the entrance of a single pollen tube into one female gametophyte. To prevent polyspermy, Arabidopsis ovules avoid the attraction of multiple pollen tubes to one ovule–polytubey block. In Arabidopsis jagger mutants, a significant number of ovules attract more than one pollen tube to an ovule due to an impairment in synergid degeneration. JAGGER encodes a putative arabinogalactan protein which is predicted to be anchored to the plasma membrane by a glycosylphosphatidylinositol (GPI) anchor. Here, we show that JAGGER fused to citrine yellow fluorescent protein (JAGGER-cYFP) is functional and localizes mostly to the periphery of ovule integuments and transmitting tract cells. We further investigated the importance of GPI-anchor addition domains for JAGGER localization and function. Different JAGGER proteins with deletions in predicted ω-site regions and GPI attachment signal domain, expected to compromise the addition of the GPI anchor, led to disruption of JAGGER localization in the cell periphery. All JAGGER proteins with disrupted localization were also not able to rescue the polytubey phenotype, pointing to the importance of GPI-anchor addition to in vivo function of the JAGGER protein.

Exploring ethylene-related genes in Cannabis sativa: implications for sexual plasticity - Adrian S. Monthony; Maxime de Ronne; Davoud Torkamaneh (Plant Reproduction, 2024)

The Arabidopsis SNARE complex genes regulate the early stages of pollen–stigma interactions - Stuart R. Macgregor; Paula K. S. Beronilla; Daphne R. Goring (Plant Reproduction, 2024)

The synthesis of papaya fruit flavor-related linalool was regulated by CpTPS18 and CpNAC56 - Yuan Yao; Wenhui Fu; Yue Yu; Suyan Wan; Wenping Zhang; Ray Ming (Plant Reproduction, 2024)

Pollen viability, longevity, and function in angiosperms: key drivers and prospects for improvement - Rasha Althiab-Almasaud; Eve Teyssier; Christian Chervin; Mark A. Johnson; Jean-Claude Mollet (Plant Reproduction, 2024)

Special issue on plant reproduction research in Latin America - Natalia Pabón-Mora; C. Stewart Gillmor; Maria Helena S. Goldman; Gabriela C. Pagnussat (Plant Reproduction, 2024)

EXPANSIN15 is involved in flower and fruit development in Arabidopsis - Judith Jazmin Bernal-Gallardo; Karla L. González-Aguilera; Stefan de Folter (Plant Reproduction, 2024)
Key message EXPANSIN15 is involved in petal cell morphology and size, the fusion of the medial tissues in the gynoecium and expansion of fruit valve cells. It genetically interacts with SPATULA and FRUITFULL . Abstract Cell expansion is fundamental for the formation of plant tissues and organs, contributing to their final shape and size during development. To better understand this process in flower and fruit development, we have studied the EXPANSIN15 ( EXPA15) gene, which showed expression in petals and in the gynoecium. By analyzing expa15 mutant alleles, we found that EXPA15 is involved in petal shape and size determination, by affecting cell morphology and number. EXPA15 also has a function in fruit size, by affecting cell size and number. Furthermore, EXPA15 promotes fusion of the medial tissues in the gynoecium. In addition, we observed genetic interactions with the transcription factors SPATULA (SPT) and FRUITFULL (FUL) in gynoecium medial tissue fusion, style and stigma development and fruit development in Arabidopsis. These findings contribute to the importance of EXPANSINS in floral and fruit development in Arabidopsis.

Comparative analysis of floral transition and floral organ formation in two contrasting species: Disocactus speciosus and D. eichlamii (Cactaceae) - Cristian Genaro Ramírez-Castro; Alma Piñeyro-Nelson; Estela Sandoval-Zapotitla; Salvador Arias; Isaura Rosas-Reinhold (Plant Reproduction, 2024)
Key message Contrasting morphologies in Disocactus are the result of differential development of the vegetative and floral tissue where intercalary growth is involved, resulting in a complex structure, the floral axis. Abstract Species from the Cactaceae bear adaptations related with their growth in environments under hydric stress. These adaptations have translated into the reduction and modification of various structures such as leaves, stems, lateral branches, roots and the structuring of flowers in a so-called flower-shoot . While cacti flowers and fruits have a consistent structure with showy hermaphrodite or unisexual flowers that produce a fruit called cactidium , the developmental dynamics of vegetative and reproductive tissues comprising the reproductive unit have only been inferred through the analysis of pre-anthetic buds. Here we present a comparative analysis of two developmental series covering the early stages of flower formation and organ differentiation in Disocactus speciosus and Disocactus eichlamii, which have contrasting floral morphologies. We observe that within the areole, a shoot apical meristem commences to grow upward, producing lateral leaves with a spiral arrangement, rapidly transitioning to a floral meristem. The floral meristem produces tepal primordia and a staminal ring meristem from which numerous or few stamens develop in a centrifugal manner in D. speciosus and D. eichlamii , respectively. Also, the inferior ovary derives from the floral meristem flattening and an upward growth of the surrounding tissue of the underlying stem, producing the pericarpel. This structure is novel to cacti and lacks a clear anatomical delimitation with the carpel wall. Here, we present a first study that documents the early processes taking place during initial meristem determination related to pericarpel development and early floral organ formation in cacti until the establishment of mature floral organs.

Global gene expression profile and functional analysis reveal the conservation of reproduction-associated gene networks in Gossypium hirsutum - Sarah Muniz Nardeli; Luis Willian Pacheco Arge; Sinara Artico; Stéfanie Menezes de Moura; Diogo Antonio Tschoeke; Fernanda Alves de Freitas Guedes; Maria Fatima Grossi-de-Sa; Adriana Pinheiro Martinelli; Marcio Alves-Ferreira (Plant Reproduction, 2024)

How to awaken a sleeping giant: antagonistic expression of Flowering locus T homologs and elements of the age-related pathway are associated with the flowering transition in Agave tequilana - Laura Hernández-Soriano; Laura Gálvez-Sandre; Emmanuel Ávila de Dios; June Simpson (Plant Reproduction, 2024)
Key message Antagonistic expression of Flowering locus T proteins and the ageing pathway via miRNAs and sugar metabolism regulate the initiation of flowering in A. tequilana . Abstract Flowering in commercial plantations of Agave tequilana signals that plants are ready to harvest for tequila production. However, time of flowering is often unpredictable and a detailed understanding of the process would be beneficial in the field, for breeding and for the development of future research. This report describes the functional analysis of A. tequilana FLOWERING LOCUS T (FT) genes by heterologous expression in A. thaliana and in situ hybridization in agave plants. The gene structures of the Agave tequilana FT family are also described and putative regulatory promoter elements were identified. Most Agave species have monocarpic, perennial life cycles that can last over 25 years during which plants do not respond to the normal environmental signals which induce flowering, suggesting that the ageing pathway as described in Arabidopsis may play an important role in determining flowering time in these species. Elements of this pathway were analyzed and in silico data is presented that supports the regulation of SQUAMOSA PROMOTER BINDING LIKE proteins (SPL), APETALA2 (AP2) proteins and members of Plant Glycoside Hydrolase Family 32 (PGHF32) by interactions with miRNAs 156, 172 and 164 during the initiation of flowering in A. tequilana .

Differentially methylated genes involved in reproduction and ploidy levels in recent diploidized and tetraploidized Eragrostis curvula genotypes - J. Carballo; A. Achilli; F. Hernández; M. Bocchini; M. C. Pasten; G. Marconi; E. Albertini; D. Zappacosta; V. Echenique (Plant Reproduction, 2024)
Epigenetics studies changes in gene activity without changes in the DNA sequence. Methylation is an epigenetic mechanism important in many pathways, such as biotic and abiotic stresses, cell division, and reproduction. Eragrostis curvula is a grass species reproducing by apomixis, a clonal reproduction by seeds. This work employed the MCSeEd technique to identify deferentially methylated positions, regions, and genes in the CG, CHG, and CHH contexts in E . curvula genotypes with similar genomic backgrounds but with different reproductive modes and ploidy levels. In this way, we focused the analysis on the cvs. Tanganyika INTA (4x, apomictic), Victoria (2x, sexual), and Bahiense (4x, apomictic). Victoria was obtained from the diploidization of Tanganyika INTA, while Bahiense was produced from the tetraploidization of Victoria. This study showed that polyploid/apomictic genotypes had more differentially methylated positions and regions than the diploid sexual ones. Interestingly, it was possible to observe fewer differentially methylated positions and regions in CG than in the other contexts, meaning CG methylation is conserved across the genotypes regardless of the ploidy level and reproductive mode. In the comparisons between sexual and apomictic genotypes, we identified differentially methylated genes involved in the reproductive pathways, specifically in meiosis, cell division, and fertilization. Another interesting observation was that several differentially methylated genes between the diploid and the original tetraploid genotype recovered their methylation status after tetraploidization, suggesting that methylation is an important mechanism involved in reproduction and ploidy changes.

The miRNA822 loaded by ARGONAUTE9 modulates the monosporic female gametogenesis in Arabidopsis thaliana - Andrea Tovar-Aguilar; Daniel Grimanelli; Gerardo Acosta-García; Jean-Philippe Vielle-Calzada; Jesús Agustín Badillo-Corona; Noé Durán-Figueroa (Plant Reproduction, 2024)

Factors specifying sex determination in maize - Cristina Guerrero-Méndez; María Jazmín Abraham-Juárez (Plant Reproduction, 2024)
Plant architecture is an important feature for agronomic performance in crops. In maize, which is a monoecious plant, separation of floral organs to produce specific gametes has been studied from different perspectives including genetic, biochemical and physiological. Maize mutants affected in floral organ development have been key to identifying genes, hormones and other factors like miRNAs important for sex determination. In this review, we describe floral organ formation in maize, representative mutants and genes identified with a function in establishing sexual identity either classified as feminizing or masculinizing, and its relationship with hormones associated with sexual organ identity as jasmonic acid, brassinosteroid and gibberellin. Finally, we discuss the challenges and scopes of future research in maize sex determination.

Evolution of major flowering pathway integrators in Orchidaceae - Yesenia Madrigal; Juan F. Alzate; Natalia Pabón-Mora (Plant Reproduction, 2024)
The Orchidaceae is a mega-diverse plant family with ca. 29,000 species with a large variety of life forms that can colonize transitory habitats. Despite this diversity, little is known about their flowering integrators in response to specific environmental factors. During the reproductive transition in flowering plants a vegetative apical meristem (SAM) transforms into an inflorescence meristem (IM) that forms bracts and flowers. In model grasses, like rice, a flowering genetic regulatory network (FGRN) controlling reproductive transitions has been identified, but little is known in the Orchidaceae. In order to analyze the players of the FRGN in orchids, we performed comprehensive phylogenetic analyses of CONSTANS-like/CONSTANS-like 4 ( COL/COL4), FLOWERING LOCUS D (FD), FLOWERING LOCUS C/FRUITFULL (FLC/FUL) and SUPRESSOR OF OVEREXPRESSION OF CONSTANS 1 ( SOC1) gene lineages. In addition to PEBP and AGL24 /SVP genes previously analyzed, here we identify an increase of orchid homologs belonging to COL4, and FUL gene lineages in comparison with other monocots, including grasses, due to orchid-specific gene lineage duplications. Contrariwise, local duplications in Orchidaceae are less frequent in the COL , FD and SOC1 gene lineages, which points to a retention of key functions under strong purifying selection in essential signaling factors. We also identified changes in the protein sequences after such duplications, variation in the evolutionary rates of resulting paralogous clades and targeted expression of isolated homologs in different orchids. Interestingly, vernalization-response genes like VERNALIZATION1 (VRN1) and FLOWERING LOCUS C (FLC) are completely lacking in orchids, or alternatively are reduced in number, as is the case of VERNALIZATION2/GHD7 (VRN2) . Our findings point to non-canonical factors sensing temperature changes in orchids during reproductive transition. Expression data of key factors gathered from Elleanthus auratiacus , a terrestrial orchid in high Andean mountains allow us to characterize which copies are actually active during flowering. Altogether, our data lays down a comprehensive framework to assess gene function of a restricted number of homologs identified more likely playing key roles during the flowering transition, and the changes of the FGRN in neotropical orchids in comparison with temperate grasses.

Seedless fruit in Annona squamosa L. is monogenic and conferred by INO locus deletion in multiple accessions - Bruno Rafael Alves Rodrigues; Charles S. Gasser; Samy Pimenta; Marlon Cristian Toledo Pereira; Silvia Nietsche (Plant Reproduction, 2024)
Key message Inheritance of the presence/absence of seeds in Annona squamosa is mediated by a single fully recessive gene and is caused by a deletion of the INNER NO OUTER ( INO ) locus. Abstract For some fruits, seedless varieties are desirable for consumption and processing. In the sugar apple tree ( Annona squamosa L.), the seedless trait in the Thai seedless (Ts) and Brazilian seedless (Bs) accessions was associated with defective ovules and an apparent deletion of the INNER NO OUTER ( INO ) ovule development gene locus. Segregation analysis of F 2 and backcross descendants of crosses of Bs to fertile wild-type varieties in this species with a multi-year generation time showed that seedlessness was recessive and controlled by a single locus. Comparison of whole genome sequence of a wild-type plant and a third accession, Hawaiian seedless (Hs), identified a 16 kilobase deletion including INO in this line. Ts and Bs lines were shown to have an identical deletion, indicating a common origin from a single deletion event. Analysis of microsatellite markers could not preclude the possibility that all three seedless accessions are vegetatively propagated clones. The sequence of the deletion site enabled a codominant assay for the wild-type and mutant genes allowing observation of complete cosegregation of the seedless/defective ovule phenotype with the INO deletion, showing maximal separation of less than 3.5 cM. The observed deletion is the only significant difference between the wild-type and Hs line over 587 kilobases, likely encompassing much more than 3.5 cM, showing that the deletion is the cause of seedless trait. The codominant markers and obtained progenies will be useful for introgression of the seedless trait into elite sugar apple lines and into other Annonas through interspecific crossings.

MsTFL1A delays flowering and regulates shoot architecture and root development in Medicago sativa - Christian D. Lorenzo; Pedro García-Gagliardi; María Laura Gobbini; Santiago N. Freytes; Mariana S. Antonietti; Estefanía Mancini; Carlos A. Dezar; Gerónimo Watson; Marcelo J. Yanovsky; Pablo D. Cerdán (Plant Reproduction, 2024)

Structural and histochemical approach to the fruit and seed diversity of Cyperaceae in an evolutionary context - Andrea G. Reutemann; Juca A. B. San Martin; Raúl E. Pozner (Plant Reproduction, 2024)

Looking for non-hermaphrodite cacti: multidisciplinary studies in Gymnocalycium bruchii endemic to central Argentina - Natalia E. Delbón; Nayla L. Aliscioni; Marina Lorenzati; Sergio García; Rodrigo B. Singer; Diego E. Gurvich (Plant Reproduction, 2024)

Synergid cell calcium oscillations refine understanding of FERONIA/LORELEI signaling during interspecific hybridization - Nathaniel Ponvert; Mark A. Johnson (Plant Reproduction, 2024)
Key message Pollen tubes from closely related species and mutants lacking pollen tube MYB transcription factors are able to initiate FER/LRE-dependent synergid cell calcium oscillations. Abstract Reproductive isolation leads to the evolution of new species; however, the molecular mechanisms that maintain reproductive barriers between sympatric species are not well defined. In flowering plants, sperm cells are immotile and are delivered to female gametes by the pollen grain. After landing on the stigmatic surface, the pollen grain germinates a polarized extension, the pollen tube, into floral tissue. After growing via polar extension to the female gametes and shuttling its cargo of sperm cells through its cytoplasm, the pollen tube signals its arrival and identity to synergid cells that flank the egg. If signaling is successful, the pollen tube and receptive synergid cell burst, and sperm cells are released for fusion with female gametes. To better understand cell–cell recognition during reproduction and how reproductive barriers are maintained between closely related species, pollen tube-initiated synergid cell calcium ion dynamics were examined during interspecific crosses. It was observed that interspecific pollen tubes successfully trigger synergid cell calcium oscillations—a hallmark of reproductive success—but signaling fails downstream of key signaling genes and sperm are not released. This work further defines pollen tube–synergid cell signaling as a critical block to interspecific hybridization and suggests that the FERONIA/LORELEI signaling mechanism plays multiple parallel roles during pollen tube reception.

Heterozygosity analysis of spontaneous 2n female gametes and centromere mapping of the diploid Hevea brasiliensis based on full-sib triploid populations - Yuan-yuan Zhang; Hong-kun Li; Xiao Huang; Yu-jiao Yuan; Xiao-fei Zhang; Xin-sheng Gao; Xiang-jun Wang; Ming-ming Wei; Hua-sun Huang; Weiguo Li (Plant Reproduction, 2024)

Darwin’s inflorescence syndrome is indeed associated with bee pollination - Marina M. Strelin; Nicolay L. da Cunha; Aimé Rubini-Pisano; Juan Fornoni; Marcelo A. Aizen (Plant Reproduction, 2024)

Epigenetics governs senescence - Ajayraj Kushwaha; Vipul Mishra; Durgesh Kumar Tripathi; Ravi Gupta; Vijay Pratap Singh (Plant Reproduction, 2024)

Comparative analysis of molecular and morphological diversity in two diploid Paspalum species (Poaceae) with contrasting mating systems - A. Verena Reutemann; Ana I. Honfi; Piyal Karunarathne; Fabiana Eckers; Diego H. Hojsgaard; Eric J. Martínez (Plant Reproduction, 2024)

Reproductive biology of the “Brazilian pine” (Araucaria angustifolia-Araucariaceae): the pollen tube growth and the seed cone development - Sofia A. Kuhn; Fernanda M. Nogueira; Tainá Schürer; Jorge E. A. Mariath (Plant Reproduction, 2024)

Arabidopsis Sar1 isoforms play redundant roles in female gametophytic development - Xin Liang; Shan-Wei Li; Jin-Li Wang; Hui-Min Zhao; Sha Li; Yan Zhang (Plant Reproduction, 2023)

Evolutionary features of microspore and pollen grain development in Cyperaceae - Danilo Massuia Rocha; Fernanda Mayara Nogueira; Thiago André; Jorge Ernesto de Araujo Mariath; André Luís Laforga Vanzela (Plant Reproduction, 2023)

Interploidy gene flow via a ‘pentaploid bridge’ and ploidy reduction in Cystopteris fragilis fern complex (Cystopteridaceae: Polypodiales) - Jan Ptáček; Libor Ekrt; Ondřej Hornych; Tomáš Urfus (Plant Reproduction, 2023)

The roles of a novel CDKB/KRP/FB3 cell cycle core complex in rice gametes and initiation of embryogenesis - Hengping Xu; Laura Bartley; Marc Libault; Venkatesan Sundaresan; Hong Fu; Scott Russell (Plant Reproduction, 2023)

A simple method for measuring pollen germination rate using machine learning - Akira Yamazaki; Ao Takezawa; Kyoka Nagasaka; Ko Motoki; Kazusa Nishimura; Ryohei Nakano; Tetsuya Nakazaki (Plant Reproduction, 2023)

The presence of β’1-COP and β’2-COP is required for female and male gametophyte development - Judit Sánchez-Simarro; Fernando Aniento; María Jesús Marcote (Plant Reproduction, 2023)
Coat protein I (COPI) and Coat protein II (COPII) coated vesicles mediate protein transport in the early secretory pathway. Although several components of COPII vesicles have been shown to have an essential role in Arabidopsis gametogenesis, the function of COPI components in gametogenesis has not been studied in detail. COPI consists of a heptameric complex made of α, β, β′, γ, δ, ɛ, and ζ-COP subunits and most subunits have several isoforms in Arabidopsis. We have found that two isoforms of the β’-COP subunit, β’1-COP and β’2-COP, are required for female and male gametophyte development. Reciprocal crosses between wild type plants and plants heterozygous for T-DNA insertions in β’1-COP and β’2-COP showed that β’1 β’2-cop gametophytes are not transmitted.

Genome-wide identification of the C2H2-Zinc finger gene family and functional validation of CsZFP7 in citrus nucellar embryogenesis - Hui-Hui Jia; Yuan-Tao Xu; Zhu-Jun Yin; Mei Qing; Kai-Dong Xie; Wen-Wu Guo; Xiao-Meng Wu (Plant Reproduction, 2023)

Correction: Regulatory dynamics of gene expression in the developing male gametophyte of Arabidopsis - Božena Klodová; David Potěšil; Lenka Steinbachová; Christos Michailidis; Ann-Cathrin Lindner; Dieter Hackenberg; Jörg D. Becker; Zbyněk Zdráhal; David Twell; David Honys (Plant Reproduction, 2023)

Chemical emasculation in cowpea (Vigna unguiculata (L.) Walp.) and dicotyledonous model species using trifluoromethanesulfonamide (TFMSA) - Yuka Sekiguchi; Benjamin Ewa Ubi; Takayoshi Ishii (Plant Reproduction, 2023)
Hybridization plays an indispensable role in creating the diversity associated with plant evolution and genetic improvement of crops. Production of hybrids requires control of pollination and avoidance of self-pollination for species that are predominantly autogamous. Hand emasculation, male sterility genes or male gametocides have been used in several plant species to induce pollen sterility. However, in cowpea ( Vigna unguiculata (L.) Walp), a self-pollinated cleistogamous dryland crop, only hand emasculation is used, but it is tedious and time-consuming. In this study, male sterility was effectively induced in cowpea and two dicotyledonous model species ( Arabidopsis thaliana (L.) Heynh. and Nicotiana benthamiana Domin) using trifluoromethanesulfonamide (TFMSA). Pollen viability assays using Alexander staining showed that 30 ml of 1000 mg/l TFMSA with two-time treatments of one-week interval at the early stage of the reproductive phase under field or greenhouse conditions induced 99% pollen sterility in cowpea. TFMSA treatment induced non-functional pollen in diploid A. thaliana at two-time treatment of 10 ml of 125–250 mg/l per plant and N. benthamiana at two-time treatment of 10 ml of 250–1000 mg/l per plant. TFMSA-treated cowpea plants produced hybrid seeds when used as the female parent in crosses with non-treated plants used as male parents, suggesting that TFMSA had no effect on female functionality in cowpea. The ease of TFMSA treatment and its effectiveness to induce pollen sterility in a wide range of cowpea genotypes, and in the two model plant species tested in this study, may expand the scope of techniques for rapid pollination control in self-pollinated species, with potential applications in plant breeding and plant reproduction science.

Disruption of pollen tube homogalacturonan synthesis relieves pollen tube penetration defects in the Arabidopsis O-FUCOSYLTRANSFERASE1 mutant - Kayleigh J. Robichaux; Devin K. Smith; Madison N. Blea; Chrystle Weigand; Jeffrey F. Harper; Ian S. Wallace (Plant Reproduction, 2023)

MLPK function is not required for self-incompatibility in the S29 haplotype of Brassica rapa L. - Mayu Ohata; Yoshinobu Takada; Yui Sato; Takumi Okamoto; Kohji Murase; Seiji Takayama; Go Suzuki; Masao Watanabe (Plant Reproduction, 2023)
Key message S 29 haplotype does not require the MLPK function for self-incompatibility in Brassica rapa . Abstract Self-incompatibility (SI) in Brassicaceae is regulated by the self-recognition mechanism, which is based on the S -haplotype-specific direct interaction of the pollen-derived ligand, SP11/SCR, and the stigma-side receptor, SRK. M locus protein kinase (MLPK) is known to be one of the positive effectors of the SI response. MLPK directly interacts with SRK, and is phosphorylated by SRK in Brassica rapa . In Brassicaceae, MLPK was demonstrated to be essential for SI in B. rapa and Brassica napus , whereas it is not essential for SI in Arabidopsis thaliana (with introduced SRK and SP11/SCR from related SI species). Little is known about what determines the need for MLPK in SI of Brassicaceae. In this study, we investigated the relationship between S -haplotype diversity and MLPK function by analyzing the SI phenotypes of different S haplotypes in a mlpk / mlpk mutant background. The results have clarified that in B. rapa , all the S haplotypes except the S 29 we tested need the MLPK function, but the S 29 haplotype does not require MLPK for the SI . Comparative analysis of MLPK-dependent and MLPK-independent S haplotype might provide new insight into the evolution of S -haplotype diversity and the molecular mechanism of SI in Brassicaceae.

Genetic control of generative cell shape by DUO1 in Arabidopsis - Abdur Rauf; Hoda Khatab; Michael Borg; David Twell (Plant Reproduction, 2023)
Key message The main features of generative cell morphogenesis, formation of a cytoplasmic projection and elongation of the GC body, operate through independent genetic pathways. Abstract Male gametogenesis in developing angiosperm pollen involves distinctive changes in cell morphogenesis. Re-shaping and elongation of the generative cell (GC) are linked to the formation of a GC cytoplasmic projection connected to the vegetative cell nucleus. Although genetic control of GC morphogenesis is unknown, we suspected the involvement of the germline-specific MYB transcription factor DUO POLLEN1 (DUO1). We used light and fluorescence microscopy to examine male germline development in pollen of wild-type Arabidopsis and in four allelic duo1 mutants expressing introduced cell markers. Our analysis shows that the undivided GC in duo1 pollen forms a cytoplasmic projection, but the cell body fails to elongate. In contrast GCs of cyclin-dependent kinase function mutants, which fail to divide like duo1 mutants, achieve normal morphogenesis. We conclude that DUO1 has an essential role in the elongation of the GC, but DUO1-independent pathways control the development of the GC cytoplasmic projection. The two main features of GC morphogenesis therefore operate through independently regulated genetic pathways.

Regulatory dynamics of gene expression in the developing male gametophyte of Arabidopsis - Božena Klodová; David Potěšil; Lenka Steinbachová; Christos Michailidis; Ann-Cathrin Lindner; Dieter Hackenberg; Jörg D. Becker; Zbyněk Zdráhal; David Twell; David Honys (Plant Reproduction, 2023)
Sexual reproduction in angiosperms requires the production and delivery of two male gametes by a three-celled haploid male gametophyte. This demands synchronized gene expression in a short developmental window to ensure double fertilization and seed set. While transcriptomic changes in developing pollen are known for Arabidopsis , no studies have integrated RNA and proteomic data in this model. Further, the role of alternative splicing has not been fully addressed, yet post-transcriptional and post-translational regulation may have a key role in gene expression dynamics during microgametogenesis. We have refined and substantially updated global transcriptomic and proteomic changes in developing pollen for two Arabidopsis accessions. Despite the superiority of RNA-seq over microarray-based platforms, we demonstrate high reproducibility and comparability. We identify thousands of long non-coding RNAs as potential regulators of pollen development, hundreds of changes in alternative splicing and provide insight into mRNA translation rate and storage in developing pollen. Our analysis delivers an integrated perspective of gene expression dynamics in developing Arabidopsis pollen and a foundation for studying the role of alternative splicing in this model.

Ontogeny of the pollinium in Hoya carnosa provides new insights into microsporogenesis - Yan-Feng Kuang; Rao-Zhen Jia; Henrik Balslev; Jing-Ping Liao (Plant Reproduction, 2023)

The hydroxyproline O-arabinosyltransferase FIN4 is required for tomato pollen intine development - Syeda Roop Fatima Jaffri; Holly Scheer; Cora A. MacAlister (Plant Reproduction, 2023)

Pollen tube invasive growth is promoted by callose - Karuna Kapoor; Anja Geitmann (Plant Reproduction, 2023)

Heat stress promotes haploid formation during CENH3-mediated genome elimination in Arabidopsis - Chunlian Jin; Limin Sun; Hoang Khai Trinh; Geelen Danny (Plant Reproduction, 2023)

Whole-mount RNA in situ hybridization technique in Torenia ovules - Shihao Su; Xuan Zhou; Tetsuya Higashiyama (Plant Reproduction, 2023)

Tracing the evolution of the plant meiotic molecular machinery - Gokilavani Thangavel; Paulo G. Hofstatter; Raphaël Mercier; André Marques (Plant Reproduction, 2023)
Meiosis is a highly conserved specialised cell division in sexual life cycles of eukaryotes, forming the base of gene reshuffling, biological diversity and evolution. Understanding meiotic machinery across different plant lineages is inevitable to understand the lineage-specific evolution of meiosis. Functional and cytogenetic studies of meiotic proteins from all plant lineage representatives are nearly impossible. So, we took advantage of the genomics revolution to search for core meiotic proteins in accumulating plant genomes by the highly sensitive homology search approaches, PSI-BLAST, HMMER and CLANS. We could find that most of the meiotic proteins are conserved in most of the lineages. Exceptionally, Arabidopsis thaliana ASY4, PHS1, PRD2, PRD3 orthologs were mostly not detected in some distant algal lineages suggesting their minimal conservation. Remarkably, an ancestral duplication of SPO11 to all eukaryotes could be confirmed. Loss of SPO11-1 in Chlorophyta and Charophyta is likely to have occurred, suggesting that SPO11-1 and SPO11-2 heterodimerisation may be a unique feature in land plants of Viridiplantae. The possible origin of the meiotic proteins described only in plants till now, DFO and HEIP1, could be traced and seems to occur in the ancestor of vascular plants and Streptophyta, respectively. Our comprehensive approach is an attempt to provide insights about meiotic core proteins and thus the conservation of meiotic pathways across plant kingdom. We hope that this will serve the meiotic community a basis for further characterisation of interesting candidates in future.

Ancestral self-compatibility facilitates the establishment of allopolyploids in Brassicaceae - Polina Yu. Novikova; Uliana K. Kolesnikova; Alison Dawn Scott (Plant Reproduction, 2023)
Self-incompatibility systems based on self-recognition evolved in hermaphroditic plants to maintain genetic variation of offspring and mitigate inbreeding depression. Despite these benefits in diploid plants, for polyploids who often face a scarcity of mating partners, self-incompatibility can thwart reproduction. In contrast, self- compatibility provides an immediate advantage: a route to reproductive viability. Thus, diploid selfing lineages may facilitate the formation of new allopolyploid species. Here, we describe the mechanism of establishment of at least four allopolyploid species in Brassicaceae ( Arabidopsis suecica , Arabidopsis kamchatica, Capsella bursa-pastoris, and Brassica napus ), in a manner dependent on the prior loss of the self-incompatibility mechanism in one of the ancestors. In each case, the degraded S -locus from one parental lineage was dominant over the functional S -locus of the outcrossing parental lineage. Such dominant loss-of-function mutations promote an immediate transition to selfing in allopolyploids and may facilitate their establishment.

Technology-driven approaches for meiosis research in tomato and wild relatives - Sander A. Peters; Charles J. Underwood (Plant Reproduction, 2023)
Meiosis is a specialized cell division during reproduction where one round of chromosomal replication is followed by genetic recombination and two rounds of segregation to generate recombined, ploidy-reduced spores. Meiosis is crucial to the generation of new allelic combinations in natural populations and artificial breeding programs. Several plant species are used in meiosis research including the cultivated tomato ( Solanum lycopersicum ) which is a globally important crop species. Here we outline the unique combination of attributes that make tomato a powerful model system for meiosis research. These include the well-characterized behavior of chromosomes during tomato meiosis, readily available genomics resources, capacity for genome editing, clonal propagation techniques, lack of recent polyploidy and the possibility to generate hybrids with twelve related wild species. We propose that further exploitation of genome bioinformatics, genome editing and artificial intelligence in tomato will help advance the field of plant meiosis research. Ultimately this will help address emerging themes including the evolution of meiosis, how recombination landscapes are determined, and the effect of temperature on meiosis.

Learning to tango with four (or more): the molecular basis of adaptation to polyploid meiosis - Kirsten Bomblies (Plant Reproduction, 2023)
Polyploidy, which arises from genome duplication, has occurred throughout the history of eukaryotes, though it is especially common in plants. The resulting increased size, heterozygosity, and complexity of the genome can be an evolutionary opportunity, facilitating diversification, adaptation and the evolution of functional novelty. On the other hand, when they first arise, polyploids face a number of challenges, one of the biggest being the meiotic pairing, recombination and segregation of the suddenly more than two copies of each chromosome, which can limit their fertility. Both for developing polyploidy as a crop improvement tool (which holds great promise due to the high and lasting multi-stress resilience of polyploids), as well as for our basic understanding of meiosis and plant evolution, we need to know both the specific nature of the challenges polyploids face, as well as how they can be overcome in evolution. In recent years there has been a dramatic uptick in our understanding of the molecular basis of polyploid adaptations to meiotic challenges, and that is the focus of this review.

Crossover patterning in plants - Andrew Lloyd (Plant Reproduction, 2023)
Key message Chromatin state, and dynamic loading of pro-crossover protein HEI10 at recombination intermediates shape meiotic chromosome patterning in plants. Abstract Meiosis is the basis of sexual reproduction, and its basic progression is conserved across eukaryote kingdoms. A key feature of meiosis is the formation of crossovers which result in the reciprocal exchange of segments of maternal and paternal chromosomes. This exchange generates chromosomes with new combinations of alleles, increasing the efficiency of both natural and artificial selection. Crossovers also form a physical link between homologous chromosomes at metaphase I which is critical for accurate chromosome segregation and fertility. The patterning of crossovers along the length of chromosomes is a highly regulated process, and our current understanding of its regulation forms the focus of this review. At the global scale, crossover patterning in plants is largely governed by the classically observed phenomena of crossover interference, crossover homeostasis and the obligatory crossover which regulate the total number of crossovers and their relative spacing. The molecular actors behind these phenomena have long remained obscure, but recent studies in plants implicate HEI10 and ZYP1 as key players in their coordination. In addition to these broad forces, a wealth of recent studies has highlighted how genomic and epigenomic features shape crossover formation at both chromosomal and local scales, revealing that crossovers are primarily located in open chromatin associated with gene promoters and terminators with low nucleosome occupancy.

Why do plants need the ZMM crossover pathway? A snapshot of meiotic recombination from the perspective of interhomolog polymorphism - Piotr A. Ziolkowski (Plant Reproduction, 2023)
At the heart of meiosis is crossover recombination, i.e., reciprocal exchange of chromosome fragments between parental genomes. Surprisingly, in most eukaryotes, including plants, several recombination pathways that can result in crossover event operate in parallel during meiosis. These pathways emerged independently in the course of evolution and perform separate functions, which directly translate into their roles in meiosis. The formation of one crossover per chromosome pair is required for proper chromosome segregation. This “obligate” crossover is ensured by the major crossover pathway in plants, and in many other eukaryotes, known as the ZMM pathway. The secondary pathways play important roles also in somatic cells and function mainly as repair mechanisms for DNA double-strand breaks (DSBs) not used for crossover formation. One of the consequences of the functional differences between ZMM and other DSB repair pathways is their distinct sensitivities to polymorphisms between homologous chromosomes. From a population genetics perspective, these differences may affect the maintenance of genetic variability. This might be of special importance when considering that a significant portion of plants uses inbreeding as a predominant reproductive strategy, which results in loss of interhomolog polymorphism. While we are still far from fully understanding the relationship between meiotic recombination pathways and genetic variation in populations, recent studies of crossovers in plants offer a new perspective.

The meiotic topoisomerase VI B subunit (MTOPVIB) is essential for meiotic DNA double-strand break formation in barley (Hordeum vulgare L.) - Stefan Steckenborn; Maria Cuacos; Mohammad A. Ayoub; Chao Feng; Veit Schubert; Iris Hoffie; Götz Hensel; Jochen Kumlehn; Stefan Heckmann (Plant Reproduction, 2023)
Key message In barley ( Hordeum vulgare ), MTOPVIB is critical for meiotic DSB and accompanied SC and CO formation while dispensable for meiotic bipolar spindle formation. Abstract Homologous recombination during meiosis assures genetic variation in offspring. Programmed meiotic DNA double-strand breaks (DSBs) are repaired as crossover (CO) or non-crossover (NCO) during meiotic recombination. The meiotic topoisomerase VI (TopoVI) B subunit (MTOPVIB) plays an essential role in meiotic DSB formation critical for CO-recombination. More recently MTOPVIB has been also shown to play a role in meiotic bipolar spindle formation in rice and maize. Here, we describe a meiotic DSB-defective mutant in barley ( Hordeum vulgare L.). CRISPR-associated 9 (Cas9) endonuclease-generated mtopVIB plants show complete sterility due to the absence of meiotic DSB, synaptonemal complex (SC), and CO formation leading to the occurrence of univalents and their unbalanced segregation into aneuploid gametes. In HvmtopVIB plants, we also frequently found the bi-orientation of sister kinetochores in univalents during metaphase I and the precocious separation of sister chromatids during anaphase I. Moreover, the near absence of polyads after meiosis II, suggests that despite being critical for meiotic DSB formation in barley, MTOPVIB seems not to be strictly required for meiotic bipolar spindle formation.

Repair of DNA double-strand breaks in plant meiosis: role of eukaryotic RecA recombinases and their modulators - Côme Emmenecker; Christine Mézard; Rajeev Kumar (Plant Reproduction, 2023)

Comparing the efficiency of six clearing methods in developing seeds of Arabidopsis thaliana - Venkata Pardha Saradhi Attuluri; Juan Francisco Sánchez López; Lukáš Maier; Kamil Paruch; Hélène S. Robert (Plant Reproduction, 2022)
Key message ClearSee alpha and FAST9 were optimized for imaging Arabidopsis seeds up to the torpedo stages. The methods preserve the fluorescence of reporter proteins and seed shape, allowing phenotyping embryos in intact seeds. Abstract Tissue clearing methods eliminate the need for sectioning, thereby helping better understand the 3D organization of tissues and organs. In the past fifteen years, clearing methods have been developed to preserve endogenous fluorescent protein tags. Some of these methods (ClearSee, TDE, PEA-Clarity, etc.) were adapted to clear various plant species, with the focus on roots, leaves, shoot apical meristems, and floral parts. However, these methods have not been used in developing seeds beyond the early globular stage. Tissue clearing is problematic in post-globular seeds due to various apoplastic barriers and secondary metabolites. In this study, we compared six methods for their efficiency in clearing Arabidopsis thaliana seeds at post-globular embryonic stages. Three methods (TDE, ClearSee, and ClearSee alpha) have already been reported in plants, whereas the others (fsDISCO, FAST9, and CHAPS clear) are used in this context for the first time. These methods were assessed for seed morphological changes, clearing capacity, removal of tannins, and spectral properties. We tested each method in seeds from globular to mature stages. The pros and cons of each method are listed herein. ClearSee alpha appears to be the method of choice as it preserves seed morphology and prevents tannin oxidation. However, FAST9 with 60% iohexol as a mounting medium is faster, clears better, and appears suitable for embryonic shape imaging. Our results may guide plant researchers to choose a suitable method for imaging fluorescent protein-labeled embryos in intact Arabidopsis seeds.

Non-photoperiodic transition of female cannabis seedlings from juvenile to adult reproductive stage - Ben Spitzer-Rimon; Hadas Shafran-Tomer; Gilad H. Gottlieb; Adi Doron-Faigenboim; Hanita Zemach; Rina Kamenetsky-Goldstein; Moshe Flaishman (Plant Reproduction, 2022)

Characterization and analysis of the promoter region of monodehydroascorbate reductase 4 (CpMDAR4) in papaya - Dessireé Zerpa-Catanho; Steven J. Clough; Ray Ming (Plant Reproduction, 2022)

The effect of the nucleotides immediately upstream of the AUG start codon on the efficiency of translation initiation in sperm cells - Jiao-Jiao Shi; Yuan Cao; Qiu-Hua Lang; Yao Dong; Liu-Yuan Huang; Liu-Jie Yang; Jing-Jing Li; Xue-Xin Zhang; Dan-Yang Wang (Plant Reproduction, 2022)

The TCP transcription factor HvTB2 heterodimerizes with VRS5 and controls spike architecture in barley - Tatiana de Souza Moraes; Sam W. van Es; Inmaculada Hernández-Pinzón; Gwendolyn K. Kirschner; Froukje van der Wal; Sylvia Rodrigues da Silveira; Jacqueline Busscher-Lange; Gerco C. Angenent; Matthew Moscou; Richard G. H. Immink; G. Wilma van Esse (Plant Reproduction, 2022)
Key message Understanding the molecular network, including protein-protein interactions, of VRS5 provide new routes towards the identification of other key regulators of plant architecture in barley. Abstract The TCP transcriptional regulator TEOSINTE BRANCHED 1 (TB1) is a key regulator of plant architecture. In barley, an important cereal crop, HvTB1 (also referred to as VULGARE SIX-ROWED spike (VRS) 5), inhibits the outgrowth of side shoots, or tillers, and grains. Despite its key role in barley development, there is limited knowledge on the molecular network that is utilized by VRS5. In this work, we performed protein–protein interaction studies of VRS5. Our analysis shows that VRS5 potentially interacts with a diverse set of proteins, including other class II TCP’s, NF-Y TF, but also chromatin remodelers. Zooming in on the interaction capacity of VRS5 with other TCP TFs shows that VRS5 preferably interacts with other class II TCP TFs in the TB1 clade. Induced mutagenesis through CRISPR–Cas of one of the putative VRS5 interactors, HvTB2 (also referred to as COMPOSITUM 1 and BRANCHED AND INDETERMINATE SPIKELET 1), resulted in plants that have lost their characteristic unbranched spike architecture. More specifically, hvtb2 mutants exhibited branches arising at the main spike, suggesting that HvTB2 acts as inhibitor of branching. Our protein–protein interaction studies of VRS5 resulted in the identification of HvTB2 as putative interactor of VRS5, another key regulator of spike architecture in barley. The study presented here provides a first step to underpin the protein–protein interactome of VRS5 and to identify other, yet unknown, key regulators of barley plant architecture.

Plastid ribosome protein L5 is essential for post-globular embryo development in Arabidopsis thaliana - Gilles Dupouy; Emma McDermott; Ronan Cashell; Anna Scian; Marcus McHale; Peter Ryder; Joelle de Groot; Noel Lucca; Galina Brychkova; Peter C. McKeown; Charles Spillane (Plant Reproduction, 2022)
Plastid ribosomal proteins (PRPs) can play essential roles in plastid ribosome functioning that affect plant function and development. However, the roles of many PRPs remain unknown, including elucidation of which PRPs are essential or display redundancy. Here, we report that the nuclear-encoded PLASTID RIBOSOMAL PROTEIN L5 (PRPL5) is essential for early embryo development in A. thaliana , as homozygous loss-of-function mutations in the PRPL5 gene impairs chloroplast development and leads to embryo failure to develop past the globular stage. We confirmed the prpl5 embryo-lethal phenotype by generating a mutant CRISPR/Cas9 line and by genetic complementation. As PRPL5 underwent transfer to the nuclear genome early in the evolution of Embryophyta , PRPL5 can be expected to have acquired a chloroplast transit peptide. We identify and validate the presence of an N-terminal chloroplast transit peptide, but unexpectedly also confirm the presence of a conserved and functional Nuclear Localization Signal on the protein C-terminal end. This study highlights the fundamental role of the plastid translation machinery during the early stages of embryo development in plants and raises the possibility of additional roles of plastid ribosomal proteins in the nucleus.

Effect of assimilate competition during early seed development on the pod and seed growth traits in soybean - Mohammad Foteh Ali; Paige Brown; John Thomas; Montserrat Salmerόn; Tomokazu Kawashima (Plant Reproduction, 2022)

Transcriptomes across fertilization and seed development in the water lily Nymphaea thermarum (Nymphaeales): evidence for epigenetic patterning during reproduction - Rebecca A. Povilus; William E. Friedman (Plant Reproduction, 2022)

DNA Methyltransferase 3 (MET3) is regulated by Polycomb group complex during Arabidopsis endosperm development - Louis Tirot; Diane M. V. Bonnet; Pauline E. Jullien (Plant Reproduction, 2022)
Complex epigenetic changes occur during plant reproduction. These regulations ensure the proper transmission of epigenetic information as well as allowing for zygotic totipotency. In Arabidopsis , the main DNA methyltransferase is called MET1 and is responsible for methylating cytosine in the CG context. The Arabidopsis genome encodes for three additional reproduction-specific homologs of MET1 , namely MET2a , MET2b and MET3. In this paper, we show that the DNA methyltransferase MET3 is expressed in the seed endosperm and its expression is later restricted to the chalazal endosperm. MET3 is biallelically expressed in the endosperm but displays a paternal expression bias. We found that MET3 expression is regulated by the Polycomb complex proteins FIE and MSI1. Seed development is not impaired in met3 mutant, and we could not observe significant transcriptional changes in met3 mutant. MET3 might regulates gene expression in a Polycomb mutant background suggesting a further complexification of the interplay between H3K27me3 and DNA methylation in the seed endosperm. Key message The DNA METHYLTRANSFERASE MET3 is controlled by Polycomb group complex during endosperm development.

Let's shape again: the concerted molecular action that builds the pollen tube - Aslıhan Çetinbaş-Genç; Veronica Conti; Giampiero Cai (Plant Reproduction, 2022)

A semi in vivo pollination technique to assess the level of gametophytic self-incompatibility and pollen tube growth in pear (Pyrus communis L.) - Hanne Claessen; Bram Van de Poel; Wannes Keulemans; Nico De Storme (Plant Reproduction, 2022)

Accumulation dynamics of ARGONAUTE proteins during meiosis in Arabidopsis - Cecilia Oliver; German Martinez (Plant Reproduction, 2022)
Meiosis is a specialized cell division that is key for reproduction and genetic diversity in sexually reproducing plants. Recently, different RNA silencing pathways have been proposed to carry a specific activity during meiosis, but the pathways involved during this process remain unclear. Here, we explored the subcellular localization of different ARGONAUTE (AGO) proteins, the main effectors of RNA silencing, during male meiosis in Arabidopsis thaliana using immunolocalizations with commercially available antibodies. We detected the presence of AGO proteins associated with posttranscriptional gene silencing (AGO1, 2, and 5) in the cytoplasm and the nucleus, while AGOs associated with transcriptional gene silencing (AGO4 and 9) localized exclusively in the nucleus. These results indicate that the localization of different AGOs correlates with their predicted roles at the transcriptional and posttranscriptional levels and provide an overview of their timing and potential role during meiosis.

Passiflora organensis FT/TFL1 gene family and their putative roles in phase transition and floral initiation - Tatiana S. Moraes; Richard G. H. Immink; Adriana P. Martinelli; Gerco C. Angenent; Wilma van Esse; Marcelo C. Dornelas (Plant Reproduction, 2022)

Dissection and ultramicroscopic observation of an apical pollen tube of Pyrus - Chenxi Shi; Demian Wang; Yaqin Guan; Haiyong Qu (Plant Reproduction, 2022)

The SEEL motif and members of the MYB-related REVEILLE transcription factor family are important for the expression of LORELEI in the synergid cells of the Arabidopsis female gametophyte - Jennifer A. Noble; Alex Seddon; Sahra Uygun; Ashley Bright; Steven E. Smith; Shin-han Shiu; Ravishankar Palanivelu (Plant Reproduction, 2022)

Dynamics of mitochondrial distribution during development and asymmetric division of rice zygotes - Hanifah Aini; Yoshikatsu Sato; Kakishi Uno; Tetsuya Higashiyama; Takashi Okamoto (Plant Reproduction, 2022)

TRM61 is essential for Arabidopsis embryo and endosperm development - Mohammad Aslam; Xiaoyi Huang; Maokai Yan; Zeyuan She; Xiangyu Lu; Beenish Fakher; Yingzhi Chen; Gang Li; Yuan Qin (Plant Reproduction, 2022)

Identification of structural variation and polymorphisms of a sex co-segregating scaffold in spinach - Li’ang Yu; Xiaokai Ma; William Wadlington; Ray Ming (Plant Reproduction, 2022)

High temperatures during microsporogenesis fatally shorten pollen lifespan - Maurizio Iovane; Giovanna Aronne (Plant Reproduction, 2022)
Many crop species are cultivated to produce seeds and/or fruits and therefore need reproductive success to occur. Previous studies proved that high temperature on mature pollen at anther dehiscence reduce viability and germinability therefore decreasing crop productivity. We hypothesized that high temperature might affect pollen functionality even if the heat treatment is exerted only during the microsporogenesis. Experimental data on Solanum lycopersicum ‘Micro-Tom’ confirmed our hypothesis. Microsporogenesis successfully occurred at both high (30 °C) and optimal (22 °C) temperature. After the anthesis, viability and germinability of the pollen developed at optimal temperature gradually decreased and the reduction was slightly higher when pollen was incubated at 30 °C. Conversely, temperature effect was eagerly enhanced in pollen developed at high temperature. In this case, a drastic reduction of viability and a drop-off to zero of germinability occurred not only when pollen was incubated at 30 °C but also at 22 °C. Further ontogenetic analyses disclosed that high temperature significantly speeded-up the microsporogenesis and the early microgametogenesis (from vacuolated stage to bi-cellular pollen); therefore, gametophytes result already senescent at flower anthesis. Our work contributes to unravel the effects of heat stress on pollen revealing that high temperature conditions during microsporogenesis prime a fatal shortening of the male gametophyte lifespan.

Correction to: Evolution and diversity of the angiosperm anther: trends in function and development - Johanna Åstrand; Christopher Knight; Jordan Robson; Behzad Talle; Zoe A. Wilson (Plant Reproduction, 2021)
Unfortunately, the original publication of the article has an error in the labelling on Fig. 3. The correct figure is given in this correction.

Flowering plant embryos: How did we end up here? - Stefan A. Rensing; Dolf Weijers (Plant Reproduction, 2021)
The seeds of flowering plants are sexually produced propagules that ensure dispersal and resilience of the next generation. Seeds harbor embryos, three dimensional structures that are often miniatures of the adult plant in terms of general structure and primordial organs. In addition, embryos contain the meristems that give rise to post-embryonically generated structures. However common, flowering plant embryos are an evolutionary derived state. Flowering plants are part of a much larger group of embryo-bearing plants, aptly termed Embryophyta. A key question is what evolutionary trajectory led to the emergence of flowering plant embryos. In this opinion, we deconstruct the flowering plant embryo and describe the current state of knowledge of embryos in other plant lineages. While we are far yet from understanding the ancestral state of plant embryogenesis, we argue what current knowledge may suggest and how the knowledge gaps may be closed.

The epigenetic origin of life history transitions in plants and algae - Jérômine Vigneau; Michael Borg (Plant Reproduction, 2021)
Plants and algae have a complex life history that transitions between distinct life forms called the sporophyte and the gametophyte. This phenomenon—called the alternation of generations—has fascinated botanists and phycologists for over 170 years. Despite the mesmerizing array of life histories described in plants and algae, we are only now beginning to learn about the molecular mechanisms controlling them and how they evolved. Epigenetic silencing plays an essential role in regulating gene expression during multicellular development in eukaryotes, raising questions about its impact on the life history strategy of plants and algae. Here, we trace the origin and function of epigenetic mechanisms across the plant kingdom, from unicellular green algae through to angiosperms, and attempt to reconstruct the evolutionary steps that influenced life history transitions during plant evolution. Central to this evolutionary scenario is the adaption of epigenetic silencing from a mechanism of genome defense to the repression and control of alternating generations. We extend our discussion beyond the green lineage and highlight the peculiar case of the brown algae. Unlike their unicellular diatom relatives, brown algae lack epigenetic silencing pathways common to animals and plants yet display complex life histories, hinting at the emergence of novel life history controls during stramenopile evolution.

Consequences of whole genome duplication for 2n pollen performance - Joseph H. Williams (Plant Reproduction, 2021)

Switching it up: algal insights into sexual transitions - Susana M. Coelho; James Umen (Plant Reproduction, 2021)
While the process of meiosis is highly conserved across eukaryotes, the sexual systems that govern life cycle phase transitions are surprisingly labile. Switches between sexual systems have profound evolutionary and ecological consequences, in particular for plants, but our understanding of the fundamental mechanisms and ultimate causes underlying these transitions is still surprisingly incomplete. We explore here the idea that brown and green algae may be interesting comparative models that can increase our understanding of relevant processes in plant reproductive biology, from evolution of gamete dimorphism, gametogenesis, sex determination and transitions in sex-determining systems.

Evolution and diversity of the angiosperm anther: trends in function and development - Johanna Åstrand; Christopher Knight; Jordan Robson; Behzad Talle; Zoe A. Wilson (Plant Reproduction, 2021)
Key message Anther development and dehiscence is considered from an evolutionary perspective to identify drivers for differentiation, functional conservation and to identify key questions for future male reproduction research. Abstract Development of viable pollen and its timely release from the anther are essential for fertilisation of angiosperm flowers. The formation and subsequent dehiscence of the anther are under tight regulatory control, and these processes are remarkably conserved throughout the diverse families of the angiosperm clade. Anther development is a complex process, which requires timely formation and communication between the multiple somatic anther cell layers (the epidermis, endothecium, middle layer and tapetum) and the developing pollen. These layers go through regulated development and selective degeneration to facilitate the formation and ultimate release of the pollen grains. Insight into the evolution and divergence of anther development and dehiscence, especially between monocots and dicots, is driving greater understanding of the male reproductive process and increased, resilient crop yields. This review focuses on anther structure from an evolutionary perspective by highlighting their diversity across plant species. We summarise new findings that illustrate the complexities of anther development and evaluate how they challenge established models of anther form and function, and how they may help to deliver future sustainable crop yields.

The emerging role of small RNAs in ovule development, a kind of magic - Rosanna Petrella; Mara Cucinotta; Marta A. Mendes; Charles J. Underwood; Lucia Colombo (Plant Reproduction, 2021)
In plants, small RNAs have been recognized as key genetic and epigenetic regulators of development. Small RNAs are usually 20 to 30 nucleotides in length and they control, in a sequence specific manner, the transcriptional or post-transcriptional expression of genes. In this review, we present a comprehensive overview of the most recent findings about the function of small RNAs in ovule development, including megasporogenesis and megagametogenesis, both in sexual and apomictic plants. We discuss recent studies on the role of miRNAs, siRNAs and trans-acting RNAs (ta-siRNAs) in early female germline differentiation. The mechanistic complexity and unique regulatory features are reviewed, and possible directions for future research are provided.

Regulation of gametangia and gametangiophore initiation in the liverwort Marchantia polymorpha - Shohei Yamaoka; Keisuke Inoue; Takashi Araki (Plant Reproduction, 2021)

Insights into the molecular evolution of fertilization mechanism in land plants - Vijyesh Sharma; Anthony J. Clark; Tomokazu Kawashima (Plant Reproduction, 2021)

The evolution of imprinting in plants: beyond the seed - Sean A. Montgomery; Frédéric Berger (Plant Reproduction, 2021)
Genomic imprinting results in the biased expression of alleles depending on if the allele was inherited from the mother or the father. Despite the prevalence of sexual reproduction across eukaryotes, imprinting is only found in placental mammals, flowering plants, and some insects, suggesting independent evolutionary origins. Numerous hypotheses have been proposed to explain the selective pressures that favour the innovation of imprinted gene expression and each differs in their experimental support and predictions. Due to the lack of investigation of imprinting in land plants, other than angiosperms with triploid endosperm, we do not know whether imprinting occurs in species lacking endosperm and with embryos developing on maternal plants. Here, we discuss the potential for uncovering additional examples of imprinting in land plants and how these observations may provide additional support for one or more existing imprinting hypotheses.

Plant sexual reproduction: perhaps the current plant two-sex model should be replaced with three- and four-sex models? - Scott T. Meissner (Plant Reproduction, 2021)
The two-sex model makes the assumption that there are only two sexual reproductive states: male and female. However, in land plants (embryophytes) the application of this model to the alternation of generations life cycle requires the subtle redefinition of several common terms related to sexual reproduction, which seems to obscure aspects of one or the other plant generation: For instance, the homosporous sporophytic plant is treated as being asexual, and the gametophytes of angiosperms treated like mere gametes. In contrast, the proposal is made that the sporophytes of homosporous plants are indeed sexual reproductive organisms, as are the gametophytes of heterosporous plants. This view requires the expansion of the number of sexual reproductive states we accept for these plant species; therefore, a three-sex model for homosporous plants and a four-sex model for heterosporous plants are described and then contrasted with the current two-sex model. These new models allow the use of sexual reproductive terms in a manner largely similar to that seen in animals, and may better accommodate the plant alternation of generations life cycle than does the current plant two-sex model. These new models may also help stimulate new lines of research, and examples of how they might alter our view of events in the flower, and may lead to new questions about sexual determination and differentiation, are presented. Thus it is suggested that land plant species have more than merely two sexual reproductive states and that recognition of this may promote our study and understanding of them.

Characterization of transcriptomic response in ovules derived from inter-subgeneric hybridization in Prunus (Rosaceae) species - Takuya Morimoto; Yuto Kitamura; Koji Numaguchi; Akihiro Itai (Plant Reproduction, 2021)

Detection of a biolistic delivery of fluorescent markers and CRISPR/Cas9 to the pollen tube - Shiori Nagahara; Tetsuya Higashiyama; Yoko Mizuta (Plant Reproduction, 2021)
Key message Biolistic delivery into pollen. Abstract In recent years, genome editing techniques, such as the CRISPR/Cas9 system, have been highlighted as a new approach to plant breeding. Agrobacterium -mediated transformation has been widely utilized to generate transgenic plants by introducing plasmid DNA containing CRISPR/Cas9 into plant cells. However, this method has general limitations, such as the limited host range of Agrobacterium and difficulties in tissue culture, including callus induction and regeneration. To avoid these issues, we developed a method to genetically modify germ cells without the need for Agrobacterium -mediated transfection and tissue culture using tobacco as a model. In this study, plasmid DNA containing sequences of Cas9, guide RNA, and fluorescent reporter was introduced into pollen using a biolistic delivery system. Based on the transient expression of fluorescent reporters, the Arabidopsis UBQ10 promoter was found to be the most suitable promoter for driving the expression of the delivered gene in pollen tubes. We also evaluated the delivery efficiency in male germ cells in the pollen by expression of the introduced fluorescent marker. Mutations were detected in the target gene in the genomic DNA extracted from CRISPR/Cas9-introduced pollen tubes, but were not detected in the negative control. Bombarded pollen germinated pollen tubes and delivered their contents into the ovules in vivo. Although it is necessary to improve biolistic delivery efficiency and establish a method for the screening of genome-modified seeds, our findings provide important insights for the detection and production of genome-modified seeds by pollen biolistic delivery.

Loss of obligate crossovers, defective cytokinesis and male sterility in barley caused by short-term heat stress - Cédric Schindfessel; Zofia Drozdowska; Len De Mooij; Danny Geelen (Plant Reproduction, 2021)

A dynamic intron retention program regulates the expression of several hundred genes during pollen meiosis - Agnieszka A. Golicz; Annapurna D. Allu; Wei Li; Neeta Lohani; Mohan B. Singh; Prem L. Bhalla (Plant Reproduction, 2021)

Conserved, divergent and heterochronic gene expression during Brachypodium and Arabidopsis embryo development - Zhaodong Hao; Zhongjuan Zhang; Daoquan Xiang; Prakash Venglat; Jinhui Chen; Peng Gao; Raju Datla; Dolf Weijers (Plant Reproduction, 2021)
Key message Developmental and transcriptomic analysis of Brachypodium embryogenesis and comparison with Arabidopsis identifies conserved and divergent phases of embryogenesis and reveals widespread heterochrony of developmental gene expression. Abstract Embryogenesis, transforming the zygote into the mature embryo, represents a fundamental process for all flowering plants. Current knowledge of cell specification and differentiation during plant embryogenesis is largely based on studies of the dicot model plant Arabidopsis thaliana . However, the major crops are monocots and the transcriptional programs associated with the differentiation processes during embryogenesis in this clade were largely unknown. Here, we combined analysis of cell division patterns with development of a temporal transcriptomic resource during embryogenesis of the monocot model plant Brachypodium distachyon . We found that early divisions of the Brachypodium embryo were highly regular, while later stages were marked by less stereotypic patterns. Comparative transcriptomic analysis between Brachypodium and Arabidopsis revealed that early and late embryogenesis shared a common transcriptional program, whereas mid-embryogenesis was divergent between species. Analysis of orthology groups revealed widespread heterochronic expression of potential developmental regulators between the species. Interestingly, Brachypodium genes tend to be expressed at earlier stages than Arabidopsis counterparts, which suggests that embryo patterning may occur early during Brachypodium embryogenesis. Detailed investigation of auxin-related genes shows that the capacity to synthesize, transport and respond to auxin is established early in the embryo. However, while early PIN1 polarity could be confirmed, it is unclear if an active response is mounted. This study presents a resource for studying Brachypodium and grass embryogenesis and shows that divergent angiosperms share a conserved genetic program that is marked by heterochronic gene expression.

A dye combination for the staining of pollen coat and pollen wall - Xin-Lei Jia; Jing-Shi Xue; Fang Zhang; Chi Yao; Shi-Yi Shen; Chang-Xu Sui; Yu-Jia Peng; Qin-Lin Xu; Yi-Feng Feng; Wen-Jing Hu; Ping Xu; Zhong-Nan Yang (Plant Reproduction, 2021)

Arabinogalactan glycoprotein dynamics during the progamic phase in the tomato pistil - Cecilia Monserrat Lara-Mondragón; Cora A. MacAlister (Plant Reproduction, 2021)

HAG1 and SWI3A/B control of male germ line development in P. patens suggests conservation of epigenetic reproductive control across land plants - Anne C. Genau; Zhanghai Li; Karen S. Renzaglia; Noe Fernandez Pozo; Fabien Nogué; Fabian B. Haas; Per K. I. Wilhelmsson; Kristian K. Ullrich; Mona Schreiber; Rabea Meyberg; Christopher Grosche; Stefan A. Rensing (Plant Reproduction, 2021)
Key message Bryophytes as models to study the male germ line: loss-of-function mutants of epigenetic regulators HAG1 and SWI3a/b demonstrate conserved function in sexual reproduction. Abstract With the water-to-land transition, land plants evolved a peculiar haplodiplontic life cycle in which both the haploid gametophyte and the diploid sporophyte are multicellular. The switch between these phases was coined alternation of generations. Several key regulators that control the bauplan of either generation are already known. Analyses of such regulators in flowering plants are difficult due to the highly reduced gametophytic generation, and the fact that loss of function of such genes often is embryo lethal in homozygous plants. Here we set out to determine gene function and conservation via studies in bryophytes. Bryophytes are sister to vascular plants and hence allow evolutionary inferences. Moreover, embryo lethal mutants can be grown and vegetatively propagated due to the dominance of the bryophyte gametophytic generation. We determined candidates by selecting single copy orthologs that are involved in transcriptional control, and of which flowering plant mutants show defects during sexual reproduction, with a focus on the under-studied male germ line. We selected two orthologs, SWI3a/b and HAG1 , and analyzed loss-of-function mutants in the moss P. patens . In both mutants, due to lack of fertile spermatozoids, fertilization and hence the switch to the diploid generation do not occur. Pp hag1 additionally shows arrested male and impaired female gametangia development. We analyzed HAG1 in the dioecious liverwort M. polymorpha and found that in Mp hag1 the development of gametangiophores is impaired. Taken together, we find that involvement of both regulators in sexual reproduction is conserved since the earliest divergence of land plants.

Deep learning-based high-throughput phenotyping can drive future discoveries in plant reproductive biology - Cedar Warman; John E. Fowler (Plant Reproduction, 2021)
Key message Advances in deep learning are providing a powerful set of image analysis tools that are readily accessible for high-throughput phenotyping applications in plant reproductive biology. High-throughput phenotyping systems are becoming critical for answering biological questions on a large scale. These systems have historically relied on traditional computer vision techniques. However, neural networks and specifically deep learning are rapidly becoming more powerful and easier to implement. Here, we examine how deep learning can drive phenotyping systems and be used to answer fundamental questions in reproductive biology. We describe previous applications of deep learning in the plant sciences, provide general recommendations for applying these methods to the study of plant reproduction, and present a case study in maize ear phenotyping. Finally, we highlight several examples where deep learning has enabled research that was previously out of reach and discuss the future outlook of these methods.

Transgenerational conditioned male fertility of HD-ZIP IV transcription factor mutant ocl4: impact on 21-nt phasiRNA accumulation in pre-meiotic maize anthers - Pranjal Yadava; Saleh Tamim; Han Zhang; Chong Teng; Xue Zhou; Blake C. Meyers; Virginia Walbot (Plant Reproduction, 2021)

Oxygen radicals and cytoplasm zoning in growing lily pollen tubes - Alexandra Podolyan; Oksana Luneva; Ekaterina Klimenko; Maria Breygina (Plant Reproduction, 2021)

Correction to: Characterization of novel pollen-expressed transcripts reveals their potential roles in pollen heat stress response in Arabidopsis thaliana - Nicholas Rutley; Laetitia Poidevin; Tirza Doniger; Richard L. Tillett; Abhishek Rath; Javier Forment; Gilad Luria; Karen A. Schlauch; Alejandro Ferrando; Jeffery F. Harper; Gad Miller (Plant Reproduction, 2021)

A simple and rapid method for imaging male meiotic cells in anthers of model and non-model plant species - Claudia Rossig; Liam Le Lievre; Sarah M. Pilkington; Lynette Brownfield (Plant Reproduction, 2021)

Oxygen, secreted proteins and small RNAs: mobile elements that govern anther development - Stefanie Dukowic-Schulze; Karina van der Linde (Plant Reproduction, 2021)
Correct anther development is essential for male fertility and subsequently agricultural yield. Defects in anther development range from the early stage of stamen formation until the late stage of tapetum degeneration. In particular, the specification of the four distinct somatic layers and the inner sporogenous cells need perfect orchestration relying on precise cell–cell communication. Up to now, several signals, which coordinate the anther´s developmental program, have been identified. Among the known signals are phytohormones, environmental conditions sensed via glutaredoxins, several receptor-like kinases triggered by ligands like MAC1, and small RNAs such as miRNAs and the monocot-prevalent reproductive phasiRNAs. Rather than giving a full review on anther development, here we discuss anther development with an emphasis on mobile elements like ROS/oxygen, secreted proteins and small RNAs (only briefly touching on phytohormones), how they might act and interact, and what the future of this research area might reveal.

Characterization of novel pollen-expressed transcripts reveals their potential roles in pollen heat stress response in Arabidopsis thaliana - Nicholas Rutley; Laetitia Poidevin; Tirza Doniger; Richard L. Tillett; Abhishek Rath; Javier Forment; Gilad Luria; Karen A. Schlauch; Alejandro Ferrando; Jeffery F. Harper; Gad Miller (Plant Reproduction, 2021)
Key message Arabidopsis pollen transcriptome analysis revealed new intergenic transcripts of unknown function, many of which are long non-coding RNAs, that may function in pollen-specific processes, including the heat stress response. Abstract The male gametophyte is the most heat sensitive of all plant tissues. In recent years, long noncoding RNAs (lncRNAs) have emerged as important components of cellular regulatory networks involved in most biological processes, including response to stress. While examining RNAseq datasets of developing and germinating Arabidopsis thaliana pollen exposed to heat stress (HS), we identified 66 novel and 246 recently annotated intergenic expressed loci (XLOCs) of unknown function, with the majority encoding lncRNAs. Comparison with HS in cauline leaves and other RNAseq experiments indicated that 74% of the 312 XLOCs are pollen-specific, and at least 42% are HS-responsive. Phylogenetic analysis revealed that 96% of the genes evolved recently in Brassicaceae . We found that 50 genes are putative targets of microRNAs and that 30% of the XLOCs contain small open reading frames (ORFs) with homology to protein sequences. Finally, RNAseq of ribosome-protected RNA fragments together with predictions of periodic footprint of the ribosome P-sites indicated that 23 of these ORFs are likely to be translated. Our findings indicate that many of the 312 unknown genes might be functional and play a significant role in pollen biology, including the HS response.

Ecological, (epi)genetic and physiological aspects of bet-hedging in angiosperms - Maraeva Gianella; Kent J. Bradford; Filippo Guzzon (Plant Reproduction, 2021)
Key message Bet-hedging is a complex evolutionary strategy involving morphological, eco-physiological, (epi)genetic and population dynamics aspects. We review these aspects in flowering plants and propose further research needed for this topic. Bet-hedging is an evolutionary strategy that reduces the temporal variance in fitness at the expense of a lowered arithmetic mean fitness. It has evolved in organisms subjected to variable cues from the external environment, be they abiotic or biotic stresses such as irregular rainfall or predation. In flowering plants, bet-hedging is exhibited by hundreds of species and is mainly exerted by reproductive organs, in particular seeds but also embryos and fruits. The main example of bet-hedging in angiosperms is diaspore heteromorphism in which the same individual produces different seed/fruit morphs in terms of morphology, dormancy, eco-physiology and/or tolerance to biotic and abiotic stresses in order to ‘hedge its bets’ in unpredictable environments. The objective of this review is to provide a comprehensive overview of the ecological, genetic, epigenetic and physiological aspects involved in shaping bet-hedging strategies, and how these can affect population dynamics. We identify several open research questions about bet-hedging strategies in plants: 1) understanding ecological trade-offs among different traits; 2) producing more comprehensive phylogenetic analyses to understand the diffusion and evolutionary implications of this strategy; 3) clarifying epigenetic mechanisms related to bet-hedging and plant responses to environmental cues; and 4) applying multi-omics approaches to study bet-hedging at different levels of detail. Clarifying those aspects of bet-hedging will deepen our understanding of this fascinating evolutionary strategy.

Comparative analyses of angiosperm secretomes identify apoplastic pollen tube functions and novel secreted peptides - María Flores-Tornero; Lele Wang; David Potěšil; Said Hafidh; Frank Vogler; Zbyněk Zdráhal; David Honys; Stefanie Sprunck; Thomas Dresselhaus (Plant Reproduction, 2021)
Key message Analyses of secretomes of in vitro grown pollen tubes from Amborella, maize and tobacco identified many components of processes associated with the cell wall, signaling and metabolism as well as novel small secreted peptides. Abstract Flowering plants (angiosperms) generate pollen grains that germinate on the stigma and produce tubes to transport their sperm cells cargo deep into the maternal reproductive tissues toward the ovules for a double fertilization process. During their journey, pollen tubes secrete many proteins (secreted proteome or secretome) required, for example, for communication with the maternal reproductive tissues, to build a solid own cell wall that withstands their high turgor pressure while softening simultaneously maternal cell wall tissue. The composition and species specificity or family specificity of the pollen tube secretome is poorly understood. Here, we provide a suitable method to obtain the pollen tube secretome from in vitro grown pollen tubes of the basal angiosperm Amborella trichopoda (Amborella) and the Poaceae model maize. The previously published secretome of tobacco pollen tubes was used as an example of eudicotyledonous plants in this comparative study. The secretome of the three species is each strongly different compared to the respective protein composition of pollen grains and tubes. In Amborella and maize, about 40% proteins are secreted by the conventional “classic” pathway and 30% by unconventional pathways. The latter pathway is expanded in tobacco. Proteins enriched in the secretome are especially involved in functions associated with the cell wall, cell surface, energy and lipid metabolism, proteolysis and redox processes. Expansins, pectin methylesterase inhibitors and RALFs are enriched in maize, while tobacco secretes many proteins involved, for example, in proteolysis and signaling. While the majority of proteins detected in the secretome occur also in pollen grains and pollen tubes, and correlate in the number of mapped peptides with relative gene expression levels, some novel secreted small proteins were identified. Moreover, the identification of secreted proteins containing pro-peptides indicates that these are processed in the apoplast. In conclusion, we provide a proteome resource from three distinct angiosperm clades that can be utilized among others to study the localization, abundance and processing of known secreted proteins and help to identify novel pollen tube secreted proteins for functional studies.

Quantitative methods in microscopy to assess pollen viability in different plant taxa - Lorenzo Ascari; Cristina Novara; Virginia Dusio; Ludovica Oddi; Consolata Siniscalco (Plant Reproduction, 2020)
High-quality pollen is a prerequisite for plant reproductive success. Pollen viability and sterility can be routinely assessed using common stains and manual microscope examination, but with low overall statistical power. Current automated methods are primarily directed towards the analysis of pollen sterility, and high throughput solutions for both pollen viability and sterility evaluation are needed that will be consistent with emerging biotechnological strategies for crop improvement. Our goal is to refine established labelling procedures for pollen, based on the combination of fluorescein (FDA) and propidium iodide (PI), and to develop automated solutions for accurately assessing pollen grain images and classifying them for quality. We used open-source software programs (CellProfiler, CellProfiler Analyst, Fiji and R) for analysis of images collected from 10 pollen taxa labelled using FDA/PI. After correcting for image background noise, pollen grain images were examined for quality employing thresholding and segmentation. Supervised and unsupervised classification of per-object features was employed for the identification of viable, dead and sterile pollen. The combination of FDA and PI dyes was able to differentiate between viable, dead and sterile pollen in all the analysed taxa. Automated image analysis and classification significantly increased the statistical power of the pollen viability assay, identifying more than 75,000 pollen grains with high accuracy ( R 2 = 0.99) when compared to classical manual counting. Overall, we provide a comprehensive set of methodologies as baseline for the automated assessment of pollen viability using fluorescence microscopy, which can be combined with manual and mechanized imaging systems in fundamental and applied research on plant biology. We also supply the complete set of pollen images (the FDA/PI pollen dataset) to the scientific community for future research.

Comparative transcriptome analysis of gynoecious and monoecious inflorescences reveals regulators involved in male flower development in the woody perennial plant Jatropha curcas - Mei-Li Zhao; Mao-Sheng Chen; Jun Ni; Chuan-Jia Xu; Qing Yang; Zeng-Fu Xu (Plant Reproduction, 2020)

Bridging the GAPs in plant reproduction: a comparison of plant and animal GPI-anchored proteins - Nicholas Desnoyer; Ravishankar Palanivelu (Plant Reproduction, 2020)

Identification of pollen and pistil polygalacturonases in Nicotiana tabacum and their function in interspecific stigma compatibility - Jugou Liao; Zhiyun Chen; Xuemei Wei; Keliang Tao; Jingwen Zhang; Xiaojun Qin; Zihui Pan; Wenguang Ma; Lei Pan; Shuai Yang; Mingqiao Wang; Xiaokun Ou; et al. (Plant Reproduction, 2020)

Insights into the molecular control of cross-incompatibility in Zea mays - Yongxian Lu; Adrienne N. Moran Lauter; Srilakshmi Makkena; M. Paul Scott; Matthew M. S. Evans (Plant Reproduction, 2020)

Expression of Brassica napus GLO1 is sufficient to breakdown artificial self-incompatibility in Arabidopsis thaliana - Patrick Kenney; Subramanian Sankaranarayanan; Michael Balogh; Emily Indriolo (Plant Reproduction, 2020)

Live Imaging of embryogenic structures in Brassica napus microspore embryo cultures highlights the developmental plasticity of induced totipotent cells - Patricia Corral-Martínez; Charlotte Siemons; Anneke Horstman; Gerco C. Angenent; Norbert de Ruijter; Kim Boutilier (Plant Reproduction, 2020)
Key message In vitro embryo development is highly plastic; embryo cell fate can be re-established in tissue culture through different pathways. Abstract In most angiosperms, embryo development from the single-celled zygote follows a defined pattern of cell divisions in which apical (embryo proper) and basal (root and suspensor) cell fates are established within the first cell divisions. By contrast, embryos that are induced in vitro in the absence of fertilization show a less regular initial cell division pattern yet develop into histodifferentiated embryos that can be converted into seedlings. We used the Brassica napus microspore embryogenesis system, in which the male gametophyte is reprogrammed in vitro to form haploid embryos, to identify the developmental fates of the different types of embryogenic structures found in culture. Using time-lapse imaging of LEAFY COTYLEDON1 -expressing cells, we show that embryogenic cell clusters with very different morphologies are able to form haploid embryos. The timing of surrounding pollen wall (exine) rupture is a major determinant of cell fate in these clusters, with early exine rupture leading to the formation of suspensor-bearing embryos and late rupture to suspensorless embryos. In addition, we show that embryogenic callus, which develops into suspensor-bearing embryos, initially expresses transcripts associated with both basal- and apical-embryo cell fates, suggesting that these two cell fates are fixed later in development. This study reveals the inherent plasticity of in vitro embryo development and identifies new pathways by which embryo cell fate can be established.

Differential cell persistence is observed in the Arabidopsis female gametophyte during heat stress - Vivek Ambastha; Yehoram Leshem (Plant Reproduction, 2020)

Intracellular dynamics and transcriptional regulations in plant zygotes: a case study of Arabidopsis - Yusuke Kimata; Minako Ueda (Plant Reproduction, 2020)

COPI complex isoforms are required for the early acceptance of compatible pollen grains in Arabidopsis thaliana - Daniel A. Cabada Gomez; M. Isabella Chavez; Alejandra N. Cobos; Roni J. Gross; Julia A. Yescas; Michael A. Balogh; Emily Indriolo (Plant Reproduction, 2020)

Melatonin in flowering, fruit set and fruit ripening - M. B. Arnao; J. Hernández-Ruiz (Plant Reproduction, 2020)

Loss of function of Oryza sativa Argonaute 18 induces male sterility and reduction in phased small RNAs - Soumita Das; Chenna Swetha; Kannan Pachamuthu; Ashwin Nair; P. V. Shivaprasad (Plant Reproduction, 2020)

Impact of whole genome triplication on the evolutionary history and the functional dynamics of regulatory genes involved in Brassica self-incompatibility signalling pathway - Thanina Azibi; Houria Hadj-Arab; Maryse Lodé; Julie Ferreira de Carvalho; Gwenn Trotoux; Sylvie Nègre; Marie-Madeleine Gilet; Julien Boutte; Jérémy Lucas; Xavier Vekemans; Anne-Marie Chèvre; Mathieu Rousseau-Gueutin (Plant Reproduction, 2020)

Correction to: Isolation of the sperm and egg cells in wild rice (Oryza officinalis) as a mechanism for crop improvement - Wei Deng; Cheng Cheng; Chengke Luo; Shu Juan Yang (Plant Reproduction, 2020)

Isolation of the sperm and egg cells in wild rice (Oryza officinalis) as a mechanism for crop improvement - Wei Deng; Cheng Cheng; Chengke Luo; Shu Juan Yang (Plant Reproduction, 2020)

Developmental basis for flower sex determination and effects of cytokinin on sex determination in Plukenetia volubilis (Euphorbiaceae) - Yan Luo; Bang-Zhen Pan; Lu Li; Chen-Xuan Yang; Zeng-Fu Xu (Plant Reproduction, 2020)
Key message Cytokinin might be an important factor to regulate floral sex at the very early stage of flower development in sacha inchi. Abstract Sacha inchi ( Plukenetia volubilis , Euphorbiaceae) is characterized by having female and male flowers in a thyrse with particular differences. The mechanisms involved in the development of unisexual flowers are very poorly understood. In this study, the inflorescence and flower development of P. volubilis were investigated using light microscopy and scanning electron microscopy. We also investigated the effects of cytokinin on flower sex determination by exogenous application of 6-benzyladenine (BA) in P. volubilis . The floral development of P. volubilis was divided into eight stages, and the first morphological divergence between the male and female flowers was found to occur at stage 3. Both female and male flowers can be structurally distinguished by differences in the shape and size of the flower apex after sepal primordia initiation. There are no traces of gynoecia in male flowers or of androecia in female flowers. Exogenous application of BA effectively induced gynoecium primordia initiation and female flower development, especially at the early flower developmental stages. We propose that flower sex is determined earlier and probably occurs before flower initiation, either prior to or at inflorescence development due to the difference in the position of the female and male primordia in the inflorescence and in the time of the female and male primordia being initiated. The influence of cytokinin on female primordia during flower development in P. volubilis strongly suggests a feminization role for cytokinin in sex determination. These results indicate that cytokinin could modify the fate of the apical meristem of male flower and promote the formation of carpel primordia in P. volubilis.

Correction to: Long-term study of a subdioecious Populus ×canescens family reveals sex lability of females and reproduction behaviour of cosexual plants - Maurizio Sabatti; Muriel Gaudet; Niels A. Müller; Birgit Kersten; Cosimo Gaudiano; Giuseppe Scarascia Mugnozza; Matthias Fladung; Isacco Beritognolo (Plant Reproduction, 2020)

Correction to: Molecular mapping of a novel male-sterile gene msNJ in soybean [Glycine max (L.) Merr.] - Zhixing Nie; Tuanjie Zhao; Meifeng Liu; Jinying Dai; Tingting He; Duo Lyu; Jinming Zhao; Shouping Yang; Junyi Gai (Plant Reproduction, 2020)

Long-term study of a subdioecious Populus ×canescens family reveals sex lability of females and reproduction behaviour of cosexual plants - Maurizio Sabatti; Muriel Gaudet; Niels A. Müller; Birgit Kersten; Cosimo Gaudiano; Giuseppe Scarascia Mugnozza; Matthias Fladung; Isacco Beritognolo (Plant Reproduction, 2020)

Does breeding system affect pollen morphology? A case study in Zygophylloideae (Zygophyllaceae) - Somayeh Naghiloo; Sedigheh Nikzat Siahkolaee (Plant Reproduction, 2019)

Molecular mapping of a novel male-sterile gene msNJ in soybean [Glycine max (L.) Merr.] - Zhixing Nie; Tuanjie Zhao; Meifeng Liu; Jinying Dai; Tingting He; Duo Lyu; Jinming Zhao; Shouping Yang; Junyi Gai (Plant Reproduction, 2019)

In silico and expression analyses of fasciclin-like arabinogalactan proteins reveal functional conservation during embryo and seed development - Mário Costa; Ana Marta Pereira; Sara Cristina Pinto; Jessy Silva; Luís Gustavo Pereira; Sílvia Coimbra (Plant Reproduction, 2019)
Key message The fasciclin-like arabinogalactan proteins organization into four groups is conserved and may be related to specific roles in developmental processes across angiosperms. Abstract Fasciclin-like arabinogalactan proteins (FLAs) are a subclass of arabinogalactan proteins (AGPs), which contain fasciclin-like domains in addition to typical AGP domains. FLAs are present across all embryophytes, and despite their low overall sequence similarity, conserved regions that define the fasciclin functional domain (FAS) have been identified, suggesting that the cell adhesion property is also conserved. FLAs in Arabidopsis have been organized into four subgroups according to the number and distribution of functional domains. Recent studies associated FLAs with cell wall-related processes where domain organization seemed to be related to functional roles. In Arabidopsis, FLAs containing a single FAS domain were found to be important for the integrity and elasticity of the plant cell wall matrix, and FLAs with two FAS domains and two AGP domains were found to be involved in maintaining proper cell expansion under salt stress conditions. The main purpose of the present work was to elucidate the expression pattern of selected FLA genes during embryo and seed development using RT-qPCR. AtFLA8 and AtFLA10, two Arabidopsis genes that stood out in previous microarray studies of embryo development, were further examined using promoter-driven gene reporter analyses. We also studied the expression of cork oak FLA genes and found that their expression partially parallels the expression patterns of the putative AtFLA orthologs. We propose that the functional organization of FLAs is conserved and may be related to fundamental aspects of embryogenesis and seed development across angiosperms. Phylogenetic studies were performed, and we show that the same basic four-subgroup organization described for Arabidopsis FLA gene classification is valid for most Arabidopsis FLA orthologs of several plant species, namely poplar, corn and cork oak.

Nicotiana tabacum pollen–pistil interactions show unexpected spatial and temporal differences in pollen tube growth among genotypes - Camila M. L. Alves; Andrzej K. Noyszewski; Alan G. Smith (Plant Reproduction, 2019)

The power of model-to-crop translation illustrated by reducing seed loss from pod shatter in oilseed rape - Pauline Stephenson; Nicola Stacey; Marie Brüser; Nick Pullen; Muhammad Ilyas; Carmel O’Neill; Rachel Wells; Lars Østergaard (Plant Reproduction, 2019)

Sex change in kiwifruit (Actinidia chinensis Planch.): a developmental framework for the bisexual to unisexual floral transition - Elisabetta Caporali; Raffaele Testolin; Simon Pierce; Alberto Spada (Plant Reproduction, 2019)

Identification of a role for an E6-like 1 gene in early pollen–stigma interactions in Arabidopsis thaliana - Jennifer Doucet; Christina Truong; Elizabeth Frank-Webb; Hyun Kyung Lee; Anna Daneva; Zhen Gao; Moritz K. Nowack; Daphne R. Goring (Plant Reproduction, 2019)

Current understanding of male sterility systems in vegetable Brassicas and their exploitation in hybrid breeding - Saurabh Singh; S. S. Dey; Reeta Bhatia; Raj Kumar; T. K. Behera (Plant Reproduction, 2019)

Arabinogalactan proteins mediate intercellular crosstalk in the ovule of apple flowers - Juan M. Losada; María Herrero (Plant Reproduction, 2019)

Transgenerational effects of inter-ploidy cross direction on reproduction and F2 seed development of Arabidopsis thaliana F1 hybrid triploids - Dorota Duszynska; Bjarni Vilhjalmsson; Rosa Castillo Bravo; Sandesh Swamidatta; Thomas E. Juenger; Mark T. A. Donoghue; Aurélie Comte; Magnus Nordborg; Timothy F. Sharbel; Galina Brychkova; Peter C. McKeown; Charles Spillane (Plant Reproduction, 2019)

Comparative development of staminate and pistillate flowers in the dioecious cactus Opuntia robusta - Rocío Hernández-Cruz; Jesús Silva-Martínez; Florencia García-Campusano; Felipe Cruz-García; Gregorio Orozco-Arroyo; Isabel Alfaro; Sonia Vázquez-Santana (Plant Reproduction, 2019)

A missense mutation of STERILE APETALA leads to female sterility in Chinese cabbage (Brassica campestris ssp. pekinensis) - Wenjie Liu; Shengnan Huang; Zhiyong Liu; Tengxue Lou; Chong Tan; Yiheng Wang; Hui Feng (Plant Reproduction, 2019)

Correction to: Transcriptomics of manually isolated Amborella trichopoda egg apparatus cells - María Flores-Tornero; Sebastian Proost; Marek Mutwil; Charles P. Scutt; Thomas Dresselhaus; Stefanie Sprunck (Plant Reproduction, 2019)

Comparative transcriptome analysis reveals new molecular pathways for cucumber genes related to sex determination - Magdalena Pawełkowicz; Leszek Pryszcz; Agnieszka Skarzyńska; Rafał K. Wóycicki; Kacper Posyniak; Jacek Rymuszka; Zbigniew Przybecki; Wojciech Pląder (Plant Reproduction, 2019)

Control of stem cell activity in the carpel margin meristem (CMM) in Arabidopsis - J. Irepan Reyes-Olalde; Stefan de Folter (Plant Reproduction, 2019)

Identification of FT family genes that respond to photoperiod, temperature and genotype in relation to flowering in cassava (Manihot esculenta, Crantz) - Oluwabusayo Sarah Adeyemo; Peter T. Hyde; Tim L. Setter (Plant Reproduction, 2019)

Gifu 2018: meeting of the International Association of Sexual Plant Reproduction Research - Tomokazu Kawashima; Mark A. Johnson (Plant Reproduction, 2019)

Differential expression of heat shock and floral regulatory genes in pseudocarpel initials of mantled female inflorescences from Elaeis guineensis Jacq. - Siew-Eng Ooi; Norashikin Sarpan; Norazlin Abdul Aziz; Azimi Nuraziyan; Meilina Ong-Abdullah (Plant Reproduction, 2019)

Complex reproductive secretions occur in all extant gymnosperm lineages: a proteomic survey of gymnosperm pollination drops - Natalie Prior; Stefan A. Little; Ian Boyes; Patrick Griffith; Chad Husby; Cary Pirone-Davies; Dennis W. Stevenson; P. Barry Tomlinson; Patrick von Aderkas (Plant Reproduction, 2019)

Comparative transcriptome analysis highlights the hormone effects on somatic embryogenesis in Catalpa bungei - Wen Liu; Changlan Wang; Xiangling Shen; Hongwei Liang; Yubing Wang; Zhengquan He; Dechun Zhang; Faju Chen (Plant Reproduction, 2019)

Special issue: cellular omics methods in plant reproduction research - Thomas Dresselhaus; Dolf Weijers (Plant Reproduction, 2019)

Gene expression atlas of embryo development in Arabidopsis - Peng Gao; Daoquan Xiang; Teagen D. Quilichini; Prakash Venglat; Prashant K. Pandey; Edwin Wang; C. Stewart Gillmor; Raju Datla (Plant Reproduction, 2019)

Step-by-step protocols for rice gamete isolation - Chenxin Li; Hengping Xu; Scott D. Russell; Venkatesan Sundaresan (Plant Reproduction, 2019)

Low-input chromatin profiling in Arabidopsis endosperm using CUT&RUN - Xiao-yu Zheng; Mary Gehring (Plant Reproduction, 2019)

Transcriptomics of manually isolated Amborella trichopoda egg apparatus cells - María Flores-Tornero; Sebastian Proost; Marek Mutwil; Charles P. Scutt; Thomas Dresselhaus; Stefanie Sprunck (Plant Reproduction, 2019)

Transcriptomics of Arabidopsis sperm cells at single-cell resolution - Chandra Shekhar Misra; Mário R. Santos; Mariana Rafael-Fernandes; Nuno P. Martins; Marta Monteiro; Jörg D. Becker (Plant Reproduction, 2019)

A simple and robust protocol for immunostaining Arabidopsis pollen nuclei - Michael Borg; Daniel Buendía; Frédéric Berger (Plant Reproduction, 2019)

The embryonic transcriptome of Arabidopsis thaliana - Falko Hofmann; Michael A. Schon; Michael D. Nodine (Plant Reproduction, 2019)

Endosperm-specific transcriptome analysis by applying the INTACT system - Gerardo Del Toro-De León; Claudia Köhler (Plant Reproduction, 2019)

Isolation of living apical and basal cell lineages of early proembryos for transcriptome analysis - Xuemei Zhou; Ce Shi; Peng Zhao; Mengxiang Sun (Plant Reproduction, 2019)

Iterative subtraction facilitates automated, quantitative analysis of multiple pollen tube growth features - Nathaniel Ponvert; Jacob Goldberg; Alexander Leydon; Mark A. Johnson (Plant Reproduction, 2019)

Adapting INTACT to analyse cell-type-specific transcriptomes and nucleocytoplasmic mRNA dynamics in the Arabidopsis embryo - Joakim Palovaara; Dolf Weijers (Plant Reproduction, 2019)

The sex-determining gene CitACS4 is a pleiotropic regulator of flower and fruit development in watermelon (Citrullus lanatus) - Encarnación Aguado; Alicia García; Susana Manzano; Juan Luis Valenzuela; Julián Cuevas; Virginia Pinillos; Manuel Jamilena (Plant Reproduction, 2018)

Epigenetic responses to abiotic stresses during reproductive development in cereals - Kevin Begcy; Thomas Dresselhaus (Plant Reproduction, 2018)

Extracellular ATP promoted pollen germination and tube growth of Nicotiana tabacum through promoting K+ and Ca2+ absorption - Yansheng Wu; Baozhi Qin; Kaili Feng; Ruolin Yan; Erfang Kang; Ting Liu; Zhonglin Shang (Plant Reproduction, 2018)

Pollen wall development in mango (Mangifera indica L., Anacardiaceae) - Jorge Lora; José I. Hormaza (Plant Reproduction, 2018)

Ethylene production and signaling in tomato (Solanum lycopersicum) pollen grains is responsive to heat stress conditions - Sridharan Jegadeesan; Avital Beery; Leviah Altahan; Shimon Meir; Etan Pressman; Nurit Firon (Plant Reproduction, 2018)

The role of reactive oxygen species in pollen germination in Picea pungens (blue spruce) - Nikita Maksimov; Anastasia Evmenyeva; Maria Breygina; Igor Yermakov (Plant Reproduction, 2018)

Seed coats as an alternative molecular factory: thinking outside the box - Edith Francoz; Loïc Lepiniec; Helen M. North (Plant Reproduction, 2018)

Maize opaque mutants are no longer so opaque - Shanshan Zhang; Junpeng Zhan; Ramin Yadegari (Plant Reproduction, 2018)

Seeds as perfect factories for developing sustainable agriculture - Gwyneth Ingram; Helen North; Loïc Lepiniec (Plant Reproduction, 2018)

Seed tissue and nutrient partitioning, a case for the nucellus - Jing Lu; Enrico Magnani (Plant Reproduction, 2018)

Molecular and epigenetic regulations and functions of the LAFL transcriptional regulators that control seed development - L. Lepiniec; M. Devic; T. J. Roscoe; D. Bouyer; D.-X. Zhou; C. Boulard; S. Baud; B. Dubreucq (Plant Reproduction, 2018)

Carbohydrate reserves and seed development: an overview - Manuel Aguirre; Edward Kiegle; Giulia Leo; Ignacio Ezquer (Plant Reproduction, 2018)

The long and winding road: transport pathways for amino acids in Arabidopsis seeds - Julia Karmann; Benedikt Müller; Ulrich Z. Hammes (Plant Reproduction, 2018)

Control of grain size in rice - Na Li; Ran Xu; Penggen Duan; Yunhai Li (Plant Reproduction, 2018)

Seeds as oil factories - Sébastien Baud (Plant Reproduction, 2018)

New insights into the metabolism of aspartate-family amino acids in plant seeds - Wenyi Wang; Mengyun Xu; Guoping Wang; Gad Galili (Plant Reproduction, 2018)

Within-clutch variability in gamete size arises from the size variation in gametangia in the marine green alga Monostroma angicava - Yusuke Horinouchi; Tatsuya Togashi (Plant Reproduction, 2018)

The early inflorescence of Arabidopsis thaliana demonstrates positional effects in floral organ growth and meristem patterning - Andrew R. G. Plackett; Stephen J. Powers; Andy L. Phillips; Zoe A. Wilson; Peter Hedden; Stephen G. Thomas (Plant Reproduction, 2018)

Calcium dynamics in tomato pollen tubes using the Yellow Cameleon 3.6 sensor - María Laura Barberini; Lorena Sigaut; Weijie Huang; Silvina Mangano; Silvina Paola Denita Juarez; Eliana Marzol; José Estevez; Mariana Obertello; Lía Pietrasanta; Weihua Tang; Jorge Muschietti (Plant Reproduction, 2018)

Role of Tulipa gesneriana TEOSINTE BRANCHED1 (TgTB1) in the control of axillary bud outgrowth in bulbs - Natalia M. Moreno-Pachon; Marie-Chantal Mutimawurugo; Eveline Heynen; Lidiya Sergeeva; Anne Benders; Ikram Blilou; Henk W. M. Hilhorst; Richard G. H. Immink (Plant Reproduction, 2018)

CRISPR/Cas9-mediated knockout of PiSSK1 reveals essential role of S-locus F-box protein-containing SCF complexes in recognition of non-self S-RNases during cross-compatible pollination in self-incompatible Petunia inflata - Linhan Sun; Teh-hui Kao (Plant Reproduction, 2018)

The role of receptor-like kinases in regulating plant male reproduction - Wenguo Cai; Dabing Zhang (Plant Reproduction, 2018)

Development of the Mitsucal computer system to identify causal mutation with a high-throughput sequencer - Takamasa Suzuki; Tsutae Kawai; Shunsuke Takemura; Marie Nishiwaki; Toshiya Suzuki; Kenzo Nakamura; Sumie Ishiguro; Tetsuya Higashiyama (Plant Reproduction, 2018)

Special issue on plant reproduction research in Asia - Meng-Xiang Sun; Wei-Cai Yang; Tetsuya Higashiyama (Plant Reproduction, 2018)

The suspensor as a model system to study the mechanism of cell fate specification during early embryogenesis - Xiongbo Peng; Meng-Xiang Sun (Plant Reproduction, 2018)

Arabinogalactan proteins and their sugar chains: functions in plant reproduction, research methods, and biosynthesis - Shihao Su; Tetsuya Higashiyama (Plant Reproduction, 2018)

Reproduction in woody perennial Citrus: an update on nucellar embryony and self-incompatibility - Siqi Zhang; Mei Liang; Nan Wang; Qiang Xu; Xiuxin Deng; Lijun Chai (Plant Reproduction, 2018)

Multilayered signaling pathways for pollen tube growth and guidance - Hong-Ju Li; Jiang-Guo Meng; Wei-Cai Yang (Plant Reproduction, 2018)

Small RNA pathways responsible for non-cell-autonomous regulation of plant reproduction - Ken-Ichi Nonomura (Plant Reproduction, 2018)

Cell cycle in egg cell and its progression during zygotic development in rice - Yumiko Sukawa; Takashi Okamoto (Plant Reproduction, 2018)

Multilayered dominance hierarchy in plant self-incompatibility - Sota Fujii; Seiji Takayama (Plant Reproduction, 2018)

Regulation of floral meristem activity through the interaction of AGAMOUS, SUPERMAN, and CLAVATA3 in Arabidopsis - Akira Uemura; Nobutoshi Yamaguchi; Yifeng Xu; WanYi Wee; Yasunori Ichihashi; Takamasa Suzuki; Arisa Shibata; Ken Shirasu; Toshiro Ito (Plant Reproduction, 2018)

Genetic and molecular characterization of photoperiod and thermo-sensitive male sterility in rice - Yourong Fan; Qifa Zhang (Plant Reproduction, 2018)

Arabidopsis thaliana MLO genes are expressed in discrete domains during reproductive development - Thomas C. Davis; Daniel S. Jones; Arianna J. Dino; Nicholas I. Cejda; Jing Yuan; Andrew C. Willoughby; Sharon A. Kessler (Plant Reproduction, 2017)

Style morphology and pollen tube pathway - M. M. Gotelli; E. C. Lattar; L. M. Zini; B. G. Galati (Plant Reproduction, 2017)

Tracking maize pollen development by the Leaf Collar Method - Kevin Begcy; Thomas Dresselhaus (Plant Reproduction, 2017)

Advances in understanding the molecular mechanisms of cytoplasmic male sterility and restoration in rice - Huiwu Tang; Yongyao Xie; Yao-Guang Liu; Letian Chen (Plant Reproduction, 2017)

Calcium controls the formation of vacuoles from mitochondria to regulate microspore development in wheat - Dong Xiao Li; Hai Yan Hu; Gan Li; Zhen Gang Ru; Hui Qiao Tian (Plant Reproduction, 2017)

Developmental landmarks during floral ontogeny of jalapeño chili pepper (Capsicum annuum L.) and the effect of gibberellin on ovary growth - R. Sandoval-Oliveros; L. Guevara-Olvera; J. P. Beltrán; C. Gómez-Mena; G. Acosta-García (Plant Reproduction, 2017)

Erratum to: The long pollen tube journey and in vitro pollen germination of Phalaenopsis orchids - Jhun-Chen Chen; Su-Chiung Fang (Plant Reproduction, 2017)

Loss of GCS1/HAP2 does not affect the ovule-targeting behavior of pollen tubes - Taro Takahashi; Ken Honda; Toshiyuki Mori; Tomoko Igawa (Plant Reproduction, 2017)

Molecular movement in the Arabidopsis thaliana female gametophyte - Robert M. Erdmann; Anja Hoffmann; Heidi-Kristin Walter; Hans-Achim Wagenknecht; Rita Groß-Hardt; Mary Gehring (Plant Reproduction, 2017)

Sex allocation in gynodioecious Cyananthus delavayi differs between gender morphs and soil quality - Jianguo Chen; Yang Niu; Zhimin Li; Yang Yang; Hang Sun (Plant Reproduction, 2017)

Dynamics of post-translationally modified histones during barley pollen embryogenesis in the presence or absence of the epi-drug trichostatin A - Pooja Pandey; Diaa S. Daghma; Andreas Houben; Jochen Kumlehn; Michael Melzer; Twan Rutten (Plant Reproduction, 2017)

Untargeted metabolomic analysis of tomato pollen development and heat stress response - Marine J. Paupière; Florian Müller; Hanjing Li; Ivo Rieu; Yury M. Tikunov; Richard G. F. Visser; Arnaud G. Bovy (Plant Reproduction, 2017)

Evidence for post-zygotic self-incompatibility in Handroanthus impetiginosus (Bignoniaceae) - Nelson Sabino Bittencourt Júnior (Plant Reproduction, 2017)

Haploid embryo production in rice and maize induced by PsASGR-BBML transgenes - Joann A. Conner; Maricel Podio; Peggy Ozias-Akins (Plant Reproduction, 2017)

Sequencing the genomic regions flanking S-linked PvGLO sequences confirms the presence of two GLO loci, one of which lies adjacent to the style-length determinant gene CYP734A50 - Benjamin A. Burrows; Andrew G. McCubbin (Plant Reproduction, 2017)

Functional characterization of AGAMOUS-subfamily members from cotton during reproductive development and in response to plant hormones - Stéfanie Menezes de Moura; Sinara Artico; Cássio Lima; Sarah Muniz Nardeli; Ana Berbel; Osmundo Brilhante Oliveira-Neto; Maria Fátima Grossi-de-Sá; Cristina Ferrándiz; Francisco Madueño; Márcio Alves-Ferreira (Plant Reproduction, 2017)

Characterization of pollen-expressed bZIP protein interactions and the role of ATbZIP18 in the male gametophyte - Antónia Gibalová; Lenka Steinbachová; Said Hafidh; Veronika Bláhová; Zuzana Gadiou; Christos Michailidis; Karel Műller; Roman Pleskot; Nikoleta Dupľáková; David Honys (Plant Reproduction, 2017)

The sweet cherry (Prunus avium) FLOWERING LOCUS T gene is expressed during floral bud determination and can promote flowering in a winter-annual Arabidopsis accession - Antonia Yarur; Esteban Soto; Gabriel León; Andrea Miyasaka Almeida (Plant Reproduction, 2016)

A mutational approach for the detection of genetic factors affecting seed size in maize - Stefano Sangiorgio; Laura Carabelli; Damiano Gabotti; Priscilla Sofia Manzotti; Martina Persico; Gabriella Consonni; Giuseppe Gavazzi (Plant Reproduction, 2016)

Application of rice microspore-preferred promoters to manipulate early pollen development in Arabidopsis: a heterologous system - Tien Dung Nguyen; Sunok Moon; Moe Moe Oo; Rupesh Tayade; Moon-Soo Soh; Jong Tae Song; Sung Aeong Oh; Ki Hong Jung; Soon Ki Park (Plant Reproduction, 2016)

SUMO proteases OTS1 and 2 control filament elongation through a DELLA-dependent mechanism - Alberto Campanaro; Raffaella Battaglia; Massimo Galbiati; Ari Sadanandom; Chiara Tonelli; Lucio Conti (Plant Reproduction, 2016)

A transcriptomic resource for Douglas-fir seed development and analysis of transcription during late megagametophyte development - Stefan A. Little; Ian G. Boyes; Kate Donaleshen; Patrick von Aderkas; Jürgen Ehlting (Plant Reproduction, 2016)

Mechanisms of endosperm initiation - Philip Hands; David S. Rabiger; Anna Koltunow (Plant Reproduction, 2016)

Epigenetic marks in the Hyacinthus orientalis L. mature pollen grain and during in vitro pollen tube growth - Marlena Kozłowska; Katarzyna Niedojadło; Marta Brzostek; Elżbieta Bednarska-Kozakiewicz (Plant Reproduction, 2016)

Expression analysis of KDEL-CysEPs programmed cell death markers during reproduction in Arabidopsis - Liang-Zi Zhou; Timo Höwing; Benedikt Müller; Ulrich Z. Hammes; Christine Gietl; Thomas Dresselhaus (Plant Reproduction, 2016)

Identification of a novel MLPK homologous gene MLPKn1 and its expression analysis in Brassica oleracea - Qiguo Gao; Songmei Shi; Yudong Liu; Quanming Pu; Xiaohuan Liu; Ying Zhang; Liquan Zhu (Plant Reproduction, 2016)

Genetic interactions of the unfinished flower development (ufd) mutant support a significant role of the tomato UFD gene in regulating floral organogenesis - Sandra Poyatos-Pertíñez; Muriel Quinet; Ana Ortíz-Atienza; Sandra Bretones; Fernando J. Yuste-Lisbona; Rafael Lozano (Plant Reproduction, 2016)

Pollen as a target of environmental changes - Anil Grover; David Twell; Enrico Schleiff (Plant Reproduction, 2016)

Pollen proteomics: from stress physiology to developmental priming - Palak Chaturvedi; Arindam Ghatak; Wolfram Weckwerth (Plant Reproduction, 2016)

Bioinformatics resources for pollen - Luca Ambrosino; Hamed Bostan; Valentino Ruggieri; Maria Luisa Chiusano (Plant Reproduction, 2016)

Acclimation to high temperature during pollen development - Florian Müller; Ivo Rieu (Plant Reproduction, 2016)

Unfolded protein response in pollen development and heat stress tolerance - Sotirios Fragkostefanakis; Anida Mesihovic; Yangjie Hu; Enrico Schleiff (Plant Reproduction, 2016)

Diversification of fruit shape in the Brassicaceae family - Łukasz Łangowski; Nicola Stacey; Lars Østergaard (Plant Reproduction, 2016)

Heat stress regimes for the investigation of pollen thermotolerance in crop plants - Anida Mesihovic; Rina Iannacone; Nurit Firon; Sotirios Fragkostefanakis (Plant Reproduction, 2016)

The long pollen tube journey and in vitro pollen germination of Phalaenopsis orchids - Jhun-Chen Chen; Su-Chiung Fang (Plant Reproduction, 2016)

Sister chromatid separation and monopolar spindle organization in the first meiosis as two mechanisms of unreduced gametes formation in wheat–rye hybrids - O. G. Silkova; D. B. Loginova (Plant Reproduction, 2016)

Single-pollen genotyping to estimate mode of unreduced pollen formation in Citrus tamurana cv. Nishiuchi Konatsu - Chitose Honsho; Aisa Sakata; Hikaru Tanaka; Shuji Ishimura; Takuya Tetsumura (Plant Reproduction, 2016)

Importance of organellar proteins, protein translocation and vesicle transport routes for pollen development and function - Puneet Paul; Sascha Röth; Enrico Schleiff (Plant Reproduction, 2016)

Breeding for plant heat tolerance at vegetative and reproductive stages - Nicky Driedonks; Ivo Rieu; Wim H. Vriezen (Plant Reproduction, 2016)

New observations on gametogenic development and reproductive experimental tools to support seed yield improvement in cowpea [Vigna unguiculata (L.) Walp.] - Rigel Salinas-Gamboa; Susan D. Johnson; Nidia Sánchez-León; Anna M. G. Koltunow; Jean-Philippe Vielle-Calzada (Plant Reproduction, 2016)

Male gametophyte development and function in angiosperms: a general concept - Said Hafidh; Jan Fíla; David Honys (Plant Reproduction, 2016)

Male functions and malfunctions: the impact of phosphoinositides on pollen development and pollen tube growth - Ingo Heilmann; Till Ischebeck (Plant Reproduction, 2016)

Epigenetic events in plant male germ cell heat stress responses - Yuanyuan Chen; Florian Müller; Ivo Rieu; Peter Winter (Plant Reproduction, 2016)

Classification of EA1-box proteins and new insights into their role during reproduction in grasses - Susanne Uebler; Mihaela L. Márton; Thomas Dresselhaus (Plant Reproduction, 2015)

Tubulin cytoskeleton during microsporogenesis in the male-sterile genotype of Allium sativum and fertile Allium ampeloprasum L. - Dorota Tchórzewska; Kamil Deryło; Lidia Błaszczyk; Krystyna Winiarczyk (Plant Reproduction, 2015)

A simple and versatile cell wall staining protocol to study plant reproduction - Thomas J. Musielak; Laura Schenkel; Martina Kolb; Agnes Henschen; Martin Bayer (Plant Reproduction, 2015)

A set of domain-specific markers in the Arabidopsis embryo - Jos R. Wendrich; Barbara K. Möller; Borhan Uddin; Tatyana Radoeva; Annemarie S. Lokerse; Bert De Rybel; Dolf Weijers (Plant Reproduction, 2015)

Nuclear membrane localization during pollen development and apex-focused polarity establishment of SYP124/125 during pollen germination in Arabidopsis thaliana - Mie Ichikawa; Megumi Iwano; Masa H. Sato (Plant Reproduction, 2015)

Identification of cis-elements and evaluation of upstream regulatory region of a rice anther-specific gene, OSIPP3, conferring pollen-specific expression in Oryza sativa (L.) ssp. indica - P. Manimaran; M. Raghurami Reddy; T. Bhaskar Rao; Satendra K. Mangrauthia; R. M. Sundaram; S. M. Balachandran (Plant Reproduction, 2015)

Identification and expression analysis of BoMF25, a novel polygalacturonase gene involved in pollen development of Brassica oleracea - Meiling Lyu; Ying Liang; Youjian Yu; Zhiming Ma; Limin Song; Xiaoyan Yue; Jiashu Cao (Plant Reproduction, 2015)

Meiosis, unreduced gametes, and parthenogenesis: implications for engineering clonal seed formation in crops - Arnaud Ronceret; Jean-Philippe Vielle-Calzada (Plant Reproduction, 2015)

Reproduction and vegetative growth in the dioecious shrub Acer barbinerve in temperate forests of Northeast China - Juan Wang; Chunyu Zhang; Klaus V. Gadow; Yanxia Cheng; Xiuhai Zhao (Plant Reproduction, 2015)

A decade of pollen transcriptomics - Nicholas Rutley; David Twell (Plant Reproduction, 2015)

The central cell nuclear position at the micropylar end is maintained by the balance of F-actin dynamics, but dispensable for karyogamy in Arabidopsis - Tomokazu Kawashima; Frederic Berger (Plant Reproduction, 2015)

SYBR Green-activated sorting of Arabidopsis pollen nuclei based on different DNA/RNA content - Vera K. Schoft; Nina Chumak; János Bindics; Lucyna Slusarz; David Twell; Claudia Köhler; Hisashi Tamaru (Plant Reproduction, 2015)

Generation of a homozygous fertilization-defective gcs1 mutant by heat-inducible removal of a rescue gene - Shiori Nagahara; Hidenori Takeuchi; Tetsuya Higashiyama (Plant Reproduction, 2015)

Anther development of maize (Zea mays) and longstamen rice (Oryza longistaminata) revealed by cryo-SEM, with foci on locular dehydration and pollen arrangement - Chih-Hua Tsou; Ping-Chin Cheng; Chiung-Maan Tseng; Hsiao-Jung Yen; Yu-Lan Fu; Tien-Rong You; David B. Walden (Plant Reproduction, 2015)

Networks controlling seed size in Arabidopsis - Gregorio Orozco-Arroyo; Dario Paolo; Ignacio Ezquer; Lucia Colombo (Plant Reproduction, 2015)

Arabinogalactan proteins: rising attention from plant biologists - Ana Marta Pereira; Luís Gustavo Pereira; Sílvia Coimbra (Plant Reproduction, 2015)

Structural and developmental variability in the female gametophyte of Griffithella hookeriana, Polypleurum stylosum, and Zeylanidium lichenoides and its bearing on the occurrence of single fertilization in Podostemaceae - Anita Sehgal; Neha Mann; H. Y. Mohan Ram (Plant Reproduction, 2014)

An RNA-seq transcriptome analysis of floral buds of an interspecific Brassica hybrid between B. carinata and B. napus - Pu Chu; Huijuan Liu; Qing Yang; Yankun Wang; Guixia Yan; Rongzhan Guan (Plant Reproduction, 2014)

Antipodal cells persist through fertilization in the female gametophyte of Arabidopsis - Xiaoya Song; Li Yuan; Venkatesan Sundaresan (Plant Reproduction, 2014)

Comparative cytological and transcriptomic analysis of pollen development in autotetraploid and diploid rice - Jinwen Wu; Muhammad Qasim Shahid; Haibin Guo; Wei Yin; Zhixiong Chen; Lan Wang; Xiangdong Liu; Yonggen Lu (Plant Reproduction, 2014)

OsMLO12, encoding seven transmembrane proteins, is involved with pollen hydration in rice - Jakyung Yi; Suyoung An; Gynheung An (Plant Reproduction, 2014)

Brassinosteroids promote Arabidopsis pollen germination and growth - Frank Vogler; Christina Schmalzl; Maria Englhart; Martin Bircheneder; Stefanie Sprunck (Plant Reproduction, 2014)

Pistillate flower development and pollen tube growth mode during the delayed fertilization stage in Corylus heterophylla Fisch - Jianfeng Liu; Huidi Zhang; Yunqing Cheng; Salih Kafkas; Murat Güney (Plant Reproduction, 2014)

Sucrose concentration in the growth medium affects the cell wall composition of tobacco pollen tubes - Giovanni Biagini; Claudia Faleri; Mauro Cresti; Giampiero Cai (Plant Reproduction, 2014)

High humidity partially rescues the Arabidopsis thaliana exo70A1 stigmatic defect for accepting compatible pollen - Darya Safavian; Muhammad Jamshed; Subramanian Sankaranarayanan; Emily Indriolo; Marcus A. Samuel; Daphne R. Goring (Plant Reproduction, 2014)

Transcriptional silencing of heterologous anther promoters in maize: a genetic method to replace detasseling for seed production - A. Mark Cigan; Kristin Haug-Collet; Joshua Clapp (Plant Reproduction, 2014)

Functional redundancy and/or ongoing pseudogenization among F-box protein genes expressed in Arabidopsis male gametophyte - Sobia Ikram; Monique Durandet; Simona Vesa; Serge Pereira; Philippe Guerche; Sandrine Bonhomme (Plant Reproduction, 2014)

Flower development in Coffea arabica L.: new insights into MADS-box genes - Raphael Ricon de Oliveira; Igor Cesarino; Paulo Mazzafera; Marcelo Carnier Dornelas (Plant Reproduction, 2014)

Expression patterns of conserved microRNAs in the male gametophyte of loblolly pine (Pinus taeda) - Christina R. Quinn; Rie Iriyama; Danilo D. Fernando (Plant Reproduction, 2014)

Exploring the role of a stigma-expressed plant U-box gene in the pollination responses of transgenic self-incompatible Arabidopsis thaliana - Jianfeng Zhang; Anne C. Rea; Tingdong Fu; Chaozhi Ma; June B. Nasrallah (Plant Reproduction, 2014)

Evaluation of rice promoters conferring pollen-specific expression in a heterologous system, Arabidopsis - Moe Moe Oo; Hyun-Kyung Bae; Tien Dung Nguyen; Sunok Moon; Sung Aeong Oh; Jeong Hoe Kim; Moon-Soo Soh; Jong Tae Song; Ki-Hong Jung; Soon Ki Park (Plant Reproduction, 2014)

Identification of the self-incompatibility locus F-box protein-containing complex in Petunia inflata - Shu Li; Penglin Sun; Justin Stephen Williams; Teh-hui Kao (Plant Reproduction, 2014)

Polyploids as a “model system” for the study of heterosis - Jacob D. Washburn; James A. Birchler (Plant Reproduction, 2014)

Genetic and cellular analysis of cross-incompatibility in Zea mays - Yongxian Lu; Jerry L. Kermicle; Matthew M. S. Evans (Plant Reproduction, 2014)

Arabidopsis Fused kinase TWO-IN-ONE dominantly inhibits male meiotic cytokinesis - Sung Aeong Oh; Valérie Bourdon; Hugh G. Dickinson; David Twell; Soon Ki Park (Plant Reproduction, 2014)

The oxidative damage initiation hypothesis for meiosis - Elvira Hörandl; Franz Hadacek (Plant Reproduction, 2013)

The transmitting tissue of Nicotiana tabacum is not essential to pollen tube growth, and its ablation can reverse prezygotic interspecific barriers - Alan G. Smith; Carrie A. Eberle; Nicole G. Moss; Neil O. Anderson; Benjamin M. Clasen; Adrian D. Hegeman (Plant Reproduction, 2013)

Maize Male sterile 8 (Ms8), a putative β-1,3-galactosyltransferase, modulates cell division, expansion, and differentiation during early maize anther development - Dongxue Wang; David S. Skibbe; Virginia Walbot (Plant Reproduction, 2013)

Parental genetic distance and patterns in nonrandom mating and seed yield in predominately selfing Arabidopsis thaliana - Ann L. Carlson; Hui Gong; Christopher Toomajian; Robert J. Swanson (Plant Reproduction, 2013)

On the origin and evolution of apomixis in Boechera - John T. Lovell; Olawale M. Aliyu; Martin Mau; M. Eric Schranz; Marcus Koch; Christiane Kiefer; Bao-Hua Song; Thomas Mitchell-Olds; Timothy F. Sharbel (Plant Reproduction, 2013)

De novo zygotic transcription in wheat (Triticum aestivum L.) includes genes encoding small putative secreted peptides and a protein involved in proteasomal degradation - Dunja Leljak-Levanić; Martina Juranić; Stefanie Sprunck (Plant Reproduction, 2013)

Harnessing plant reproduction for crop improvement: an introduction to the special issue - Thomas Dresselhaus; Emidio Albertini (Plant Reproduction, 2013)

SGO1 but not SGO2 is required for maintenance of centromere cohesion in Arabidopsis thaliana meiosis - L. Zamariola; N. De Storme; CL. Tiang; S. J. Armstrong; F. C. H. Franklin; D. Geelen (Plant Reproduction, 2013)

Microspore embryogenesis: establishment of embryo identity and pattern in culture - Mercedes Soriano; Hui Li; Kim Boutilier (Plant Reproduction, 2013)

Control of the meiotic cell division program in plants - Erik Wijnker; Arp Schnittger (Plant Reproduction, 2013)

Apomixis in plant reproduction: a novel perspective on an old dilemma - Gianni Barcaccia; Emidio Albertini (Plant Reproduction, 2013)

Computational identification of conserved microRNAs and their putative targets in the Hypericum perforatum L. flower transcriptome - Giulio Galla; Mirko Volpato; Timothy F. Sharbel; Gianni Barcaccia (Plant Reproduction, 2013)

PsPMEP, a pollen-specific pectin methylesterase of pea (Pisum sativum L.) - María Dolores Gómez; Begoña Renau-Morata; Edelín Roque; Julio Polaina; José Pío Beltrán; Luis A. Cañas (Plant Reproduction, 2013)

Microspore embryogenesis in wheat: new marker genes for early, middle and late stages of embryo development - Rosa Angélica Sánchez-Díaz; Ana María Castillo; María Pilar Vallés (Plant Reproduction, 2013)

External application of gametophyte-specific ZmPMEI1 induces pollen tube burst in maize - Mayada Woriedh; Sebastian Wolf; Mihaela L. Márton; Axel Hinze; Manfred Gahrtz; Dirk Becker; Thomas Dresselhaus (Plant Reproduction, 2013)

Failure of androgenesis in Miscanthus × giganteus in vitro culture of cytologically unbalanced microspores - Iwona Żur; Ewa Dubas; Aneta Słomka; Franciszek Dubert; Elżbieta Kuta; Agnieszka Płażek (Plant Reproduction, 2013)

Arabinogalactan protein profiles and distribution patterns during microspore embryogenesis and pollen development in Brassica napus - Ahmed-Abdalla El-Tantawy; María-Teresa Solís; Mario L. Da Costa; Silvia Coimbra; María-Carmen Risueño; Pilar S. Testillano (Plant Reproduction, 2013)

Note from Editor-in-Chief - Dolf Weijers (Plant Reproduction, 2013)

Transgenic manipulation of plant embryo sacs tracked through cell-type-specific fluorescent markers: cell labeling, cell ablation, and adventitious embryos - Shai J. Lawit; Mark A. Chamberlin; April Agee; Eric S. Caswell; Marc C. Albertsen (Plant Reproduction, 2013)

Genetic separation of autonomous endosperm formation (AutE) from the two other components of apomixis in Hieracium - Daisuke Ogawa; Susan D. Johnson; Steven T. Henderson; Anna M. G. Koltunow (Plant Reproduction, 2013)

Isolation and characterization of multiple F-box genes linked to the S 9 - and S 10 -RNase in apple (Malus × domestica Borkh.) - Kazuma Okada; Shigeki Moriya; Takashi Haji; Kazuyuki Abe (Plant Reproduction, 2013)

Pollen tube entry into the synergid cell of Arabidopsis is observed at a site distinct from the filiform apparatus - Yehoram Leshem; Cameron Johnson; Venkatesan Sundaresan (Plant Reproduction, 2013)

Volume-based pollen size analysis: an advanced method to assess somatic and gametophytic ploidy in flowering plants - Nico De Storme; Linda Zamariola; Martin Mau; Timothy F. Sharbel; Danny Geelen (Plant Reproduction, 2013)

Arabidopsis RPG1 is important for primexine deposition and functions redundantly with RPG2 for plant fertility at the late reproductive stage - Ming-Xi Sun; Xue-Yong Huang; Jun Yang; Yue-Feng Guan; Zhong-Nan Yang (Plant Reproduction, 2013)

Message from the new Editor-in-Chief - Dolf Weijers (Plant Reproduction, 2013)

Defects in cytoskeletal microtubule deployment of microsporocytes contribute to fertility loss in genic male-sterile Chinese cabbage - Shao Fu; Ya Nan Zhang; Ya Ying Wang; Xue Yi Zhu; Hui Qiao Tian; Scott D. Russell (Plant Reproduction, 2013)

Polyploidy and polyembryony in Anemopaegma (Bignonieae, Bignoniaceae) - Fabiana Firetti-Leggieri; Lúcia G. Lohmann; Suzana Alcantara; Itayguara Ribeiro da Costa; João Semir (Plant Reproduction, 2013)

Chromosome pairing in meiosis of partially fertile wheat/rye hybrids - O. G. Silkova; I. G. Adonina; E. A. Krivosheina; A. I. Shchapova; V. K. Shumny (Plant Reproduction, 2013)

Wide hybridization between oat and pearl millet belonging to different subfamilies of Poaceae - Takayoshi Ishii; Hiroyuki Tanaka; Amin Elsadig Eltayeb; Hisashi Tsujimoto (Plant Reproduction, 2013)

Secretions from the female gametophyte and their role in spermatozoid induction in Cycas revoluta - Tokushiro Takaso; Yukitoshi Kimoto; John N. Owens; Masumi Kono; Tetsuro Mimura (Plant Reproduction, 2013)

Sexual isolation in two bee-pollinated Costus (Costaceae) - Grace F. Chen (Plant Reproduction, 2013)